Breeding ecology of the Atlas Pied Flycatcher Ficedula speculigera in an old oak Quercus suber forest in northeastern Algeria - Boudeffa, Khaled; Brahmia, Zahra; Benyacoub, Slim (Bird Study, 2014)
Capsule Low clutch size (CS) in the Atlas Pied Flycatcher breeding in evergreen Mediterranean forest was compensated for by relatively high overall reproductive success. Aims To describe the breeding ecology of the Atlas Pied Flycatcher Ficedula speculigera in detail for the first time, in an old oak Quercus suber forest. Methods A total of 102 nests were monitored during 2010?2012. Breeding phenology, population density, clutch and brood sizes, egg biometrics, breeding losses and breeding success were accurately determined. Results The species arrived in the breeding area in late April. Population density was very high with 4.87 (±1.02) pairs/ha. Mean egg laying date (LD) was 19 May and CS averaged 4.92 eggs. Hatching and fledging success were 88.7% and 83.5%, respectively. The number of fledged young averaged 3.8 (±1.66) and decreased with LD (4.2?±?1.45 chicks fledged per nest at the start of the season versus 2.8?±?1.56 at the end). Conclusion Lower CS compared to Ficedula hypoleuca populations was compensated by relatively high fledging success, thereby ensuring overall reproductive success of this species. Moreover, the Atlas Pied Flycatchers seem to benefit from the lower seasonality in their food in the evergreen habitat.
Keywords: clutch size; Cork oak; mediterranean forest

A comprehensive assessment of the transcriptome of cork oak (Quercus suber) through EST sequencing. - Pereira-Leal, José B; Abreu, Isabel a; Alabaça, Cláudia S; Almeida, Maria Helena; Almeida, Paulo; Almeida, Tânia; Amorim, Maria Isabel; Araújo, Susana; Azevedo, Herlânder; Badia, Aleix; Batista, Dora; Bohn, Andreas; et al. (BMC genomics, 2014)
BACKGROUND: Cork oak (Quercus suber) is one of the rare trees with the ability to produce cork, a material widely used to make wine bottle stoppers, flooring and insulation materials, among many other uses. The molecular mechanisms of cork formation are still poorly understood, in great part due to the difficulty in studying a species with a long life-cycle and for which there is scarce molecular/genomic information. Cork oak forests are of great ecological importance and represent a major economic and social resource in Southern Europe and Northern Africa. However, global warming is threatening the cork oak forests by imposing thermal, hydric and many types of novel biotic stresses. Despite the economic and social value of the Q. suber species, few genomic resources have been developed, useful for biotechnological applications and improved forest management. RESULTS: We generated in excess of 7 million sequence reads, by pyrosequencing 21 normalized cDNA libraries derived from multiple Q. suber tissues and organs, developmental stages and physiological conditions. We deployed a stringent sequence processing and assembly pipeline that resulted in the identification of ~159,000 unigenes. These were annotated according to their similarity to known plant genes, to known Interpro domains, GO classes and E.C. numbers. The phylogenetic extent of this ESTs set was investigated, and we found that cork oak revealed a significant new gene space that is not covered by other model species or EST sequencing projects. The raw data, as well as the full annotated assembly, are now available to the community in a dedicated web portal at http://www.corkoakdb.org. CONCLUSIONS: This genomic resource represents the first trancriptome study in a cork producing species. It can be explored to develop new tools and approaches to understand stress responses and developmental processes in forest trees, as well as the molecular cascades underlying cork differentiation and disease response.
APS
Keywords: Cork oak; EST sequencing; Quercus suber; transcriptome

Development of a robust chromatographic method for the detection of chlorophenols in cork oak forest soils. - McLellan, Iain; Hursthouse, Andrew; Morrison, Calum; Varela, Adélia; Pereira, Cristina Silva (Environmental monitoring and assessment, 2014)
A major concern for the cork and wine industry is 'cork taint' which is associated with chloroanisoles, the microbial degradation metabolites of chlorophenols. The use of chlorophenolic compounds as pesticides within cork forests was prohibited in 1993 in the European Union (EU) following the introduction of industry guidance. However, cork produced outside the EU is still thought to be affected and simple, robust methods for chlorophenol analysis are required for wider environmental assessment by industry and local environmental regulators. Soil samples were collected from three common-use forests in Tunisia and from one privately owned forest in Sardinia, providing examples of varied management practice and degree of human intervention. These provided challenge samples for the optimisation of a HPLC-UV detection method. It produced recoveries consistently >75 % against a soil CRM (ERM-CC008) for pentachlorophenol. The optimised method, with ultraviolet (diode array) detection is able to separate and quantify 16 different chlorophenols at field concentrations greater than the limits of detection ranging from 6.5 to 191.3 μg/kg (dry weight). Application to a range of field samples demonstrated the absence of widespread contamination in forest soils at sites sampled in Sardinia and Tunisia.
Keywords: chlorophenols; Cork oak; hplc; method development; NATO Science for peace; Quercus Suber L; soils

Effects of forest certification on the ecological condition of Mediterranean streams - Dias, Filipe S.; Bugalho, Miguel N.; Rodríguez-González, Patricia M.; Albuquerque, António; Cerdeira, J. Orestes (Journal of Applied Ecology, 2014)
1. Forest certification, a proxy for sustainable forest management, covers more than 10% of the world’s forests. Under forest certification, forest managers and landowners must comply with environmental, economic and social management standards aiming to promote forest conservation. Despite an increasing area of certified forests, there is a dearth of data on how forest certification is affecting the conservation of forest ecosystems and associated habitats. 2. Here, we assess the effects of Forest Stewardship Council (FSC) certification, one of the largest certification schemes in the world, on the ecological condition of streams crossing Mediterranean evergreen oak woodlands. 3. We used the Stream Visual Assessment Protocol (SVAP) to compare the ecological condi- tion of streams located in areas with 3 and 5 years of certification, in non-certified areas and in least disturbed streams. 4. Forest certification positively affected the ecological condition of the surveyed streams, but its effects were only measurable after 5 years of certification. Streams with 5 years of certification had more continuous, dense and diverse riparian vegetation when compared to streams located in non-certified areas. Moreover, the condition of streams located in areas with 5 years of forest certification was similar to the condition of least disturbed streams. 5. Synthesis and applications. Forest certification promotes the ecological condition of streams occurring within Mediterranean evergreen oak woodlands. This mainly happens because in areas under forest certification, managers and landowners have to comply with management practices that require them to remove or reduce the main causes for stream deg- radation, allowing riparian habitats to recover. Within landscapes with large and increasing areas under forest certification, such as the Mediterranean cork oak woodlands, the positive effects of certification on the ecological condition of streams may spread across the hydro- graphic network in the medium to long term.
Keywords: Cork oak; Forest management; Forest Stewardship Council; freshwater habitats; rapid bio-assessment protocol; Riparian vegetation; Stream Visual Assessment Protocol

Environmental risk assessment of carbosulfan on target and non-target beetles when used as white grub larvicide in the cork oak forest of Mamora (Morocco) - Fegrouche, R; Kadiri, N; Ghailoule, D; Kadiri, Z Atay; Lumaret, J -P. (INTERNATIONAL JOURNAL OF PEST MANAGEMENT, 2014)
The protection of new cork oak plantations against the larvae of the beetle Sphodroxia maroccana (Melolonthidae), which destroy the roots of newly planted trees, was provided for many years in the forest of Mamora in Morocco by the use of carbosulfan, usually formulated as dry granules for direct incorporation into the soil at planting. Ecotoxicological tests were conducted in the laboratory on S. maroccana and on two non-target beetle species, namely Pachychila obtusecostata and Pimelia platynota (Tenebrionidae), to measure the acute effects of carbosulfan and evaluate the potential risk associated with inappropriate practices. The mortality was measured at both 4 d and 7 d after ingestion of a known quantity of carbosulfan. The recommended dose by the manufacturer was exceeded by at least four-fold in the Mamora Forest, with obvious environmental risks. Risks were identified for wildlife when the pesticide is misused and spread on the soil around the plants.
Keywords: carbosulfan; Cork oak; environmental risk; Melolonthidae; Morocco; mortality; Pachychila obtusecostata; Pimelia platynota; Sphodroxia maroccana; Tenebrionidae

First report of Laimaphelenchus heidelbergi (Nematoda: Aphelenchoididae) in Europe - Maleita, C; Costa, S R; Abrantes, I (Forest Pathology, 2014)
A survey of nematodes associated with branches of cork oak, Quercus suber, a species in decline since the second half of the 20th century, was conducted on two farms located in Alentejo, Portugal. Using specific morphological characters, some nematodes were identified as belonging to the genus Laimaphelenchus and one of the isolates being identified as L. heidelbergi. This research aimed to characterize the Portuguese L. heidelbergi isolate using morphobiometrical and molecular analyses and to analyze its phylogenetic relationship to other Laimaphelenchus spp. Morphometric and morphological characteristics of L. heidelbergi females and males were similar to the original description. For molecular analyses, the mitochondrial DNA region from the cytochrome oxidase subunit I and the D2/D3 expansion segments of the large subunit of rDNA were amplified and sequenced. In phylogenetic analyses, sequences of the Portuguese L. heidelbergi isolate clustered with sequences from the Australian isolate. Laimaphelenchus heidelbergi was originally described from wood of Pinus radiata growing in Australia and is here reported for the first time in Europe and Portugal. Cork oak is a new host record for L. heidelbergi.
APS
Keywords: Alentejo; Cork oak; decline; Laimaphelenchus; mitochondrial DNA; morphological characters; nematodes; Quercus suber

Soil Bradyrhizobium population response to invasion of a natural Quercus suber forest by the introduced nitrogen-fixing tree Acacia mearnsii in El Kala National Park, Algeria - Boudiaf, Imène; Le, Christine; Baudoin, Ezekiel; Galiana, Antoine; Beddiar, Arifa; Prin, Yves; Duponnois, Robin; Le Roux, Christine; Baudoin, Ezekiel; Galiana, Antoine; Beddiar, Arifa; Prin, Yves; et al. (Soil Biology and Biochemistry, 2014)
We analyzed the diversity and identity of the rhizobial populations nodulating an invasive Australian legume tree Acacia mearnsii in a natural Quercus suber forest in the El Kala National Park, Algeria. Soils from three different forest plots corresponding to non invaded original Q. suber stand, partially invaded by A. mearnsii, and totally invaded (monodominant) A. mearnsii stand were used to trap nodulating bacteria with the same tree species. Symbiotic nitrogen-fixing bacteria were isolated from root nodules and characterized by sequencing of the internal transcribed spacer region, then submitted to phylogenetic analyses. A total of 67 isolates was obtained, representing the 3 different forest plots, all renodulating A. mearnsii in monoxenic conditions. Phylogenetic analyses showed that all isolates belong to different Bradyrhizobium lineages, according to each of the three locations with little intermixing between forest plots. These results illustrate the adaptation of nodulating Bradyrhizobium populations to the new soil conditions induced by invasion. This symbiotic adaptability is presumed to be a key factor of the invasive character of this tree species.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Cork oak; Exotic; Invasivity; Mimosoideae; Nodulation; North Africa; Rhizobia

Efeito da Intervenção Cultural na Caracterização Morfológica de Diferentes Proveniências de Quercus suber - Patrício, Sameiro; Nunes, Luís; Almeida, Helena (Silva Lusitana, 2013)
The cork oak (Quercus suber L.) is a very important species in Mediterranean areas for economic, ecological and environmental reasons. It is a species with high potential of expansion considering the scenarios of climate change. Despite its importance, cork oak adaptability to environmental conditions is poorly understood. In order to understand the genetic determinism of adaptive traits and study patterns of adaptive variation at landscape level, assuming there is genetic differentiation in phenological traits found at the population level, we established a trial in Mogadouro – Trás-os-Montes, with 34 provenances of Q. suber from its natural Mediterranean distribution area. Considering that not only the adaptation of the species, but also the improvement of the reproductive material both in tree form and quality of cork are important, and that the improvement of the tree form can be artificially induced by training technique, in this work we tested the influence of training cuts to improve tree form of the provenances. Morphological characterization of the provenances was performed using the evaluation of qualitative characteristics of the stem as inclination and dominance of the stem using a scale of 1 (worst feature) 6 values (best feature), before the cuts and five years after its application. Tree training seems to have no effect or have very little effect on the ranking of the provenances that have previously revealed the worst morphological characteristics as the group of the Italian and French and some provenances of the groups of Portuguese and Spanish. The Moroccan provenances show good adaptive features that are enhanced by training cuts.
Keywords: adaptive characteristics; Cork oak; provenance trial; training cuts; tree form

Expression of DNA methyltransferases is involved in Quercus suber cork quality - Ramos, Miguel; Rocheta, Margarida; Carvalho, Luísa; Inácio, Vera; Graça, José; Morais-Cecílio, Leonor (Tree Genetics & Genomes, 2013)
Abstract Cork oak (Quercus suber ) is an important Portuguese species, mainly due to the economic value of the cork it produces. Cork results from phellogen, a meristematic tissue, which can locally produce lenticels or have discontinu- ities, originating “defects”: pores and nail inclusions that are detrimental to cork industrial use. Epigenetic processes control plant development and its deregulation can lead to altered phenotypes; therefore, the study of epigenetic players in the phellogen is important to understand the emergence of cork's defects. DNA methyltransferases (DNMTs) and one protein associated to MET1 (DMAP1) were characterized in Q. suber, and their gene expression was analyzed in phellogen and con- tiguous differentiating cell layers of trees producing high and low quality cork, after the evaluation of their defects by physical and image analysis methods. All classes of DNMTs (MET, DRM, and CMT) with the respective canonical motifs were identified in Q. suber. The expression analyses of these genes showed that QsDRM2 was the most active methyltransferases in the cells analyzed, and that all the genes were differentially expressed in trees with distinct cork quality,with a tendency for higher expression levels in lowquality producers. Interestingly, the global methylation level was higher in cells with low expression of DNA methyltransferases. A positive and significant correlation was obtained between QsDMAP1 gene expression and the percentage of cork defects. This work provides the first evidence that cork quality in Q. suber is likely influenced by epigenetic mechanisms
Keywords: CMT3; Cork oak; Cork quality; DMAP1; DRM; MET1; MET2; phellogen activity

First Report of Root Rot Caused by Pythium spiculum Affecting Cork Oaks at Donana Biological Reserve in Spain - De Vita, P.; Serrano, M. S.; Ramo, C.; Aponte, C.; Garcia, L. V.; Belbahri, L.; Sanchez, M. E. (PLANT DISEASE, 2013)
APSAPSThe following values have no corresponding Zotero field: pub-location: 3340 PILOT KNOB ROAD, ST PAUL, MN 55121 USA publisher: AMER PHYTOPATHOLOGICAL SOC
Keywords: Cork oak; Donana Biological Reserve; Pythium spiculum; Spain

Methods : An Application in Portugal - Borges, Jose G.; Garcia-gonzalo, Jordi; Bushenkov, Vladimir; Mcdill, Marc E.; Marques, Susete; Oliveira, Manuela M. (Forest Science, 2013)
The practice of multicriteria forest management planning is often complicated by the need to explicit a priori goals and preferences of the decisionmaker. This manuscript aims at describing an approach that may take advantage of a posteriori preference modeling to facilitate the specification of the levels of achievement of various objectives in a typical forest management planning framework. The goal is to provide information about nondominated points in the feasible set in the criteria space (FSCS) so that decisionmakers may take advantage of trade-off information. The emphasis is on demonstrating the potential of adaptive search methods to enhance decisions when three or more criteria are considered. The approach combines the use of mathematical programming and interactive decision maps techniques. It is shown how the estimation refinement method may be used to approximate the Pareto frontier of a typical model I linear programming model. It is further shown how the feasible goals method/interactive decision maps method may be used to retrieve a solution selected by stakeholders from interactive decision maps depicting the Pareto frontier. Results are discussed for a large-scale test application encompassing over 1 million ha of cork and holm oak forest ecosystems in southern Portugal. FOR.SCI.
Keywords: Cork oak; forest management planning; multiple criteria decisionmaking; Pareto frontier methods

Methods : An Application in Portugal - Borges, José G; Garcia-gonzalo, Jordi; Bushenkov, Vladimir; Mcdill, Marc E; Marques, Susete; Oliveira, Manuela M (Forest Science, 2013)
The practice of multicriteria forest management planning is often complicated by the need to explicit a priori goals and preferences of the decisionmaker. This manuscript aims at describing an approach that may take advantage of a posteriori preference modeling to facilitate the specification of the levels of achievement of various objectives in a typical forest management planning framework. The goal is to provide information about nondominated points in the feasible set in the criteria space (FSCS) so that decisionmakers may take advantage of trade-off information. The emphasis is on demonstrating the potential of adaptive search methods to enhance decisions when three or more criteria are considered. The approach combines the use of mathematical programming and interactive decision maps techniques. It is shown how the estimation refinement method may be used to approximate the Pareto frontier of a typical model I linear programming model. It is further shown how the feasible goals method/interactive decision maps method may be used to retrieve a solution selected by stakeholders from interactive decision maps depicting the Pareto frontier. Results are discussed for a large-scale test application encompassing over 1 million ha of cork and holm oak forest ecosystems in southern Portugal. FOR.SCI.
Keywords: Cork oak; forest management planning; multiple criteria decisionmaking; Pareto frontier methods

Modelling the nesting-habitat of the Cinereous Vulture Aegypius monachus on a fine scale for conservation purposes - Guerrero-Casado, Jose; Arenas, Rafael; Tortosa, Francisco S. (BIRD STUDY, 2013)
Capsule Nests of Cinereous Vultures were found to be located farther from roads, villages and the edge of large vegetation patches. They preferred large vegetation patches containing extensive Cork Oak cover on steeper slopes and with lower solar radiation. Less than 8% of the study area was predicted to be suitable for nesting.Aims To generate a predictive habitat suitability map for the Cinereous Vulture's nesting-habitat on a fine scale for conservation applications within its breeding range.Methods Habitat features of 43 nest-locations and random points were compared in order to identify nest-habitat selected in the region of the Hornachuelos Natural Park (Spain). A logistic regression approach was used to create habitat models.Results Compared with random points, nests were found to be located farther from roads, villages and patch edges, and in large vegetation patches containing extensive Cork Oak cover on steeper slopes with lower solar radiation. The predictive map revealed that less than 8% of the study area had a greater probability of occupancy than 0.8.Conclusions Most habitats in the study area are unsuitable for nesting suggesting that conservation of the best suitable areas is important. The fine-scale predictive map approach may be valuable in designating conservation priority areas.
APSAPSThe following values have no corresponding Zotero field: pub-location: 4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND publisher: TAYLOR & FRANCIS LTD
Keywords: Capsule nests; Cork oak; habitat modelling; Spain

Photosynthesis of Quercus suber is affected by atmospheric NH3 generated by multifunctional agrosystems - Pintó-Marijuan, Marta; Da Silva, Anabela Bernardes; Flexas, Jaume; Dias, Teresa; Zarrouk, Olfa; Martins-Loução, Maria Amélia; Chaves, Maria Manuela; Cruz, Cristina (Tree Physiology, 2013)
Montados are evergreen oak woodlands dominated by Quercus species, which are considered to be key to biodiversity conservation and ecosystem services. This ecosystem is often used for cattle breeding in most regions of the Iberian Peninsula, which causes plants to receive extra nitrogen as ammonia (NH3) through the atmosphere. The effect of this atmospheric NH3 (NH3atm) on ecosystems is still under discussion. This study aimed to evaluate the effects of an NH3atm concentration gradient downwind of a cattle barn in a Montado area. Leaves from the selected Quercus suber L. trees along the gradient showed a clear influence of the NH3 on δ13C, as a consequence of a strong limitation on the photosynthetic machinery by a reduction of both stomatal and mesophyll conductance. A detailed study of the impact of NH3atm on the photosynthetic performance of Q. suber trees is presented, and new mechanisms by which NH3 affects photosynthesis at the leaf level are suggested.
10.1093/treephys/tpt077
Keywords: carbon isotopic discrimination; Cork oak; mesophyll conductance; Stomatal conductance

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Transpiration in Quercus suber trees under shallow water table conditions: the role of soil and groundwater - Pinto, Clara A.; Nadezhdina, Nadezhda; David, Jorge S; Kurz-Besson, Cathy; Caldeira, Maria C; Henriques, Manuel O; Monteiro, Fernando G; Pereira, João S; David, Teresa S (Hydrological Processes, 2013)
Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on two types of root behaviour: shallow connected and deep connected. Although this significantly improved knowledge on the functional traits of Mediterranean Q. suber, the approach has the limitation of requiring root sap flow data, which are seldom available. In this work, we present alternative methodologies to assess if trees are connected to groundwater and to estimate the soil and groundwater contributions to tree transpiration. We provide evidence on the tree unrestricted access to groundwater solely based on meteorological, stem sap flow and leaf water potential data. Using a soil mass balance approach, we estimated the yearly soil and groundwater contributions to tree transpiration: 69.7% and 30.3%, respectively. Groundwater uptake became dominant in the dry summer: 73.2% of tree transpiration. Results reproduce extremely well those derived from root modelling. Because of its simplicity both in formulation and data requirements, our approach is potentially liable to be adapted to other groundwater- dependent Mediterranean oak sites, where interactions between land use and water resources may be relevant.
Keywords: Cork oak; ecohydrology; sap flow radial profile; tree water sources; tree water use; water balance

Contribution of cork oak plantations installed after 1990 in Portugal to the Kyoto commitments and to the landowners economy - Coelho, Marta Baptista; Paulo, Joana Amaral; Palma, João Henrique Nunes; Tomé, Margarida (Forest Policy and Economics, 2012)
Cork oak stands are a part of the agroforestry ecosystem in Portugal, characterized by a low crown cover from cork oak trees, managed towards cork production, and sometimes in combination with grazing. In recent years, European Union policies gave impetus to a large area of new cork oak plantations, which have been established mainly for cork production purposes, and consequently with higher stand density than traditional agroforestry systems. These plantations are important not only for cork production but also for the carbon sequestered by these slow growing forests that won't be harvested for wood production. Thinning operations will be needed to avoid excessive inter-tree competition and wood extracted from these thinning may also provide income for the owners. In the present study, carbon sequestered and wood volumes resulting from thinning were estimated for the next 70 years. Three scenarios of different annual afforestation rates and different site indexes were tested. The resulting values for the considered scenarios show that, if the plantation rates are maintained, new cork oak plantations will have an important contribution to the Portuguese commitments to providing CO2 offsets under the Kyoto protocol. Additionally, due to the increasing values of initial density in new cork plantations, cork oak forests will produce a signiﬁcant volume of wood that may become an important contribution to the landowners' income.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Carbon Sequestration; Cork oak; Kyoto protocol; New plantations area; Wood

Cork Oak Vulnerability to Fire: The Role of Bark Harvesting, Tree Characteristics and Abiotic Factors - Catry, Filipe X; Moreira, Francisco; Pausas, Juli G; Fernandes, Paulo M; Rego, Francisco; Cardillo, Enrique; Curt, Thomas (PLoS ONE, 2012)
Forest ecosystems where periodical tree bark harvesting is a major economic activity may be particularly vulnerable to disturbances such as fire, since debarking usually reduces tree vigour and protection against external agents. In this paper we asked how cork oak Quercus suber trees respond after wildfires and, in particular, how bark harvesting affects post-fire tree survival and resprouting. We gathered data from 22 wildfires (4585 trees) that occurred in three southern European countries (Portugal, Spain and France), covering a wide range of conditions characteristic of Q. suber ecosystems. Post-fire tree responses (tree mortality, stem mortality and crown resprouting) were examined in relation to management and ecological factors using generalized linear mixed-effects models. Results showed that bark thickness and bark harvesting are major factors affecting resistance of Q. suber to fire. Fire vulnerability was higher for trees with thin bark (young or recently debarked individuals) and decreased with increasing bark thickness until cork was 3–4 cm thick. This bark thickness corresponds to the moment when exploited trees are debarked again, meaning that exploited trees are vulnerable to fire during a longer period. Exploited trees were also more likely to be top-killed than unexploited trees, even for the same bark thickness. Additionally, vulnerability to fire increased with burn severity and with tree diameter, and was higher in trees burned in early summer or located in drier south-facing aspects. We provided tree response models useful to help estimating the impact of fire and to support management decisions. The results suggested that an appropriate management of surface fuels and changes in the bark harvesting regime (e.g. debarking coexisting trees in different years or increasing the harvesting cycle) would decrease vulnerability to fire and contribute to the conservation of cork oak ecosystems.
Keywords: bark tickness; cork harvesting; Cork oak; fire; fire vulnerability; management (voyant); mortality; post-fire response

The diversification of terpene emissions in Mediterranean oaks: lessons from a study of Quercus suber, Quercus canariensis and its hybrid Quercus afares - Welter, Saskia; Bracho-Nuñez, Araceli; Mir, Celine; Zimmer, Ina; Kesselmeier, Jürgen; Lumaret, Roselyne; Schnitzler, Jörg-Peter; Staudt, Michael (Tree Physiology, 2012)
Interspecific gene flow is common in oaks. In the Mediterranean, this process produced geographical differentiations and new species, which may have contributed to the diversification of the production of volatile terpenes in the oak species of this region. The endemic North African deciduous oak Quercus afares (Pomel) is considered to be a stabilized hybrid between the evergreen Quercus suber (L.) and the deciduous Quercus canariensis (Willd.), presumably being monoterpene and isoprene emitters, respectively. In a common garden experiment, we examined the terpene emission capacities, terpene synthase (TPS) activities and nuclear genetic markers in 52 trees of these three oak species. All but one of the Q. suber and Q. canariensis trees were found to be genetically pure, whereas most Q. afares trees possessed a mixed genotype with a predominance of Q. suber alleles. Analysis of the foliar terpene emissions and TPS activities revealed that all the Q. canariensis trees strongly produced isoprene while all the Q. suber trees were strong monoterpene producers. Quercus afares trees produced monoterpenes as well but at more variable and significantly lower rates, and with a monoterpene pattern different than that observed in Q. suber. Among 17 individuals tested, one Q. afares tree emitted only an insignificant amount of terpenes. No mixed isoprene/monoterpene emitter was detected. Our results suggest that the capacity and pattern of volatile terpene production in Algerian Q. afares populations have strongly diverged from those of its parental species and became quantitatively and qualitatively reduced, including the complete suppression of isoprene production.
10.1093/treephys/tps06910.1093/treephys/tps069
Keywords: Algerian oak; allozyme polymorphism; chemo-taxonomy; chemotype; Cork oak; isoprene synthase; isoprenoid; speciation

Improved Genetic Transformation of Cork Oak (Quercus suber L.) - Álvarez-Fernández, Rubén; Ordás, Ricardo-Javier (Plant Cell Culture Protocols SE - 28, 2012)
An Agrobacterium-mediated transformation system for selected mature Quercus suber L. trees has been established. Leaf-derived somatic embryos in an early stage of development are inoculated with an AGL1 strain harboring a kanamycin-selectable plasmid carrying the gene of interest. The transformed embryos are induced to germinate and the plantlets transferred to soil. This protocol, from adult cork oak to transformed plantlet, can be completed in about one and a half years. Transformation efficiencies (i.e., percentage of inoculated explants that yield independent transgenic embryogenic lines) vary depending on the cork oak genotype, reaching up to 43%.
The following values have no corresponding Zotero field: periodical: Plant Cell Culture Protocols SE - 28 electronic-resource-num: 10.1007/978-1-61779-818-4_28
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; Herbicide Resistance; kanamycin resistance; Quercus suber; Somatic embryogenesis; Tree genetic transformation

Molecular characterization of Quercus suber MYB1, a transcription factor up-regulated in cork tissues - Almeida, Tânia; Menéndez, Esther; Capote, Tiago; Ribeiro, Teresa; Santos, Conceição; Gonçalves, Sónia (Journal of Plant Physiology, 2012)
The molecular processes associated with cork development in Quercus suber L. are poorly understood. A previous molecular approach identiﬁed a list of genes potentially important for cork formation and differentiation, providing a new basis for further molecular studies. This report is the ﬁrst molecular characterization of one of these candidate genes, QsMYB1, coding for an R2R3-MYB transcription factor. The R2R3-MYB gene sub-family has been described as being involved in the phenylpropanoid and lignin pathways, both involved in cork biosynthesis. The results showed that the expression of QsMYB1 is putatively mediated by an alternative splicing (AS) mechanism that originates two different transcripts (QsMYB1.1 and QsMYB1.2), differing only in the 5 -untranslated region, due to retention of the ﬁrst intron in one of the variants. Moreover, within the retained intron, a simple sequence repeat (SSR) was identiﬁed. The upstream regulatory region of QsMYB1 was extended by a genome walking approach, which allowed the identiﬁcation of the putative gene promoter region. The relative expression pattern of QsMYB1 transcripts determined by reverse transcription quantitative polymerase chain reaction (RTqPCR) revealed that both transcripts were up-regulated in cork tissues; the detected expression was several times higher in newly formed cork harvested from trees producing virgin, second or reproduction cork when compared with wood. Moreover, the expression analysis of QsMYB1 in several Q. suber organs showed very low expression in young branches and roots, whereas in leaves, immature acorns or male ﬂowers, no expression was detected. These preliminary results suggest that QsMYB1 may be related to secondary growth and, in particular, with the cork biosynthesis process with a possible alternative splicing mechanism associated with its regulatory function.
The following values have no corresponding Zotero field: accession-num: 23218545
Keywords: Alternative Splicing; Amino Acid Sequence; Cork biosynthesis; Cork oak; Gene Expression Regulation; Genes; Lipids; Lipids: biosynthesis; Molecular Sequence Data; phellogen; Plant; Plant Bark; Plant Bark: genetics; Plant Bark: metabolism; Plant Growth Regulators; Plant Growth Regulators: biosynthesis; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; RNA; Transcription Factors; Transcription Factors: chemistry; Transcription Factors: metabolism; Up-Regulation

Reference Gene Selection for Quantitative Real-time PCR Normalization in Quercus suber - Marum, Liliana; Miguel, Andreia; Ricardo, Cândido P.; Miguel, Célia (PLoS ONE, 2012)
The use of reverse transcription quantitative PCR technology to assess gene expression levels requires an accurate normalization of data in order to avoid misinterpretation of experimental results and erroneous analyses. Despite being the focus of several transcriptomics projects, oaks, and particularly cork oak (Quercus suber), have not been investigated regarding the identification of reference genes suitable for the normalization of real-time quantitative PCR data. In this study, ten candidate reference genes (Act, CACs, EF-1α, GAPDH, His3, PsaH, Sand, PP2A, ß-Tub and Ubq) were evaluated to determine the most stable internal reference for quantitative PCR normalization in cork oak. The transcript abundance of these genes was analysed in several tissues of cork oak, including leaves, reproduction cork, and periderm from branches at different developmental stages (1-, 2-, and 3-year old) or collected in different dates (active growth period versus dormancy). The three statistical methods (geNorm, NormFinder, and CV method) used in the evaluation of the most suitable combination of reference genes identified Act and CACs as the most stable candidates when all the samples were analysed together, while ß-Tub and PsaH showed the lowest expression stability. However, when different tissues, developmental stages, and collection dates were analysed separately, the reference genes exhibited some variation in their expression levels. In this study, and for the first time, we have identified and validated reference genes in cork oak that can be used for quantification of target gene expression in different tissues and experimental conditions and will be useful as a starting point for gene expression studies in other oaks.
The following values have no corresponding Zotero field: publisher: Public Library of Science
Keywords: Cork oak; Gene expression; reference genes; RT-qPCR (voyant)

Root system of Quercus suber L. seedlings in response to herbaceous competition and different watering and fertilisation regimes - Cubera, Elena; Moreno, Gerardo; Solla, Alejandro; Madeira, Manuel (Agroforestry Systems, 2012)
Different management practices are commonly applied to increase pasture yield of Mediterranean open woodlands, but the consequences of increasing competition for soil resources with these practices on tree recruitment are still unknown. In a greenhouse study, belowground competition of Quercus suber L. seedlings growing together with natural (OakNP) or improved pasture (OakIP) was evaluated, and their root systems compared with those of seedlings growing in bare soil (OakBS). Two watering levels and two regimes of P2O5 fertilisation were also tested. Because of competition, the OakIP seedlings had their ﬁne root mass density, coarse root length, and shoot mass reduced by up to 40, 36, and 39%, respectively, when compared to OakNP seedlings. OakNP and OakBS seedlings showed similar average root density parameters and shoot mass values, indicating that Q. suber seedlings growing with natural pasture is a low competitive system. High availability of water and phosphorus did not mitigate the strength of competition between herbaceous plants and oak seedlings, and favoured the pasture to the detriment of the trees. Our ﬁndings suggest that P2O5 fertilisation and irrigation practices performed to improve herbaceous productivity will negatively inﬂuence recruitment of Q. suber seedlings.
Keywords: Cork oak; Dehesa; Improved pasture; Root density; Seedling recruitment

Time to rethink the management intensity in a Mediterranean oak woodland: the response of insectivorous birds and leaf-chewing defoliators as key groups in the forest ecosystem - Pereira, Pedro; Godinho, Carlos; Roque, Inês; Marques, Ana; Branco, Manuela; Rabaça, João Eduardo (Annals of Forest Science, 2012)
Context The Iberian cork oak Quercus suber montados are dynamic agro-silvo-pastoral systems, contrasting with the abandonment trend of other Mediterranean forested areas. & Aims We aimed to identify the effect of management type and vegetation features on breeding insectivorous birds and leaf-chewing defoliator insects. & Methods In central Portugal, we selected two groups of 20 sites: dense montados (DM, high cover of cork oaks and low cattle impact) and sparse montados (SM, low cover of oaks and high cattle impact). We collected variables associated with vegetation features, bird community and chewing defoliators. & Results The two systems differed significantly in oak trunk diameter, oak and shrub cover, tree and shrub diversity. Ground bird densities were higher in SM with fragmented shrub cover. In DM, higher woody vegetation cover and diversity can promote shrub birds and leaf warblers. Oak defoliation was mainly attributed to the sawfly Periclista andrei. Sawfly defoliation was significantly higher in SM and negatively correlated with shrub cover. & Conclusions Our results highlight (1) the relevance of management activities conducted at the shrubby layer, (2) the need of an increase in tree diversity and density and (3) the maintenance of a mosaic landscape in order to improve the bird community richness and reduce the defoliation impact in montado system.
Keywords: birds; Cork oak; defoliators; management; mediterranean forest; montados

Vegetation and soil seed bank relationships across microhabitats in an abandoned Quercus suber parkland under simulated fire - Torres, Ivan; Urbieta, Itziar R; Moreno, Jose M (Ecoscience, 2012)
Mediterranean agro-forestry systems are undergoing rapid change due to abandonment. This turns formerly cultivated or grazed oak-tree parklands (i.e., savanna-type formations called “dehesas”) into flammable formations of scattered trees within a matrix of shrubs with open spaces. Wildfires can now occur, threatening the persistence of these formations. Fire-prone shrublands commonly regenerate after fire from seeds stored in the soil. Understanding the relationships between standing vegetation and the soil seed bank across microhabitats can help predict the response of the system in case of fire. Here we investigated these relationships in an abandoned Quercus suber (cork oak) dehesa in central Spain. Vegetation and soil were sampled and assigned to different microhabitats: under the trees (TRC), in dense shrub cover (DSC), and in low shrub cover (LSC). A heat shock was applied to half of each sample to simulate fire; the other half served as control. Both sets of samples were then germinated in a greenhouse. Almost 90% of the species were herbs, while the rest were woody shrubs. The number of species recorded in TRC and DSC was lower than in LSC, in which species richness, particularly herbs, was maximal. Heating increased the total number of species that germinated, but mean species richness per sample was not altered. Heating markedly increased the number of germinations in all microhabitats, particularly those of woody species. Furthermore, the germination of shrubby species increased in the 3 microhabitats, notably in TRC. While the standing plant community was well differentiated among microhabitats, this was not the case for the soil seed bank, which was homogeneous across microhabitats, with or without heating. We conclude that the high density of shrubby seeds found in TRC or in the other microhabitats presents substantial threats to the persistence of Q. suber parklands in case of fire.
Keywords: cistus; Cork oak; Dehesa; Encroachment; Erica; Mediterranean shrublands

Water stress assessment of cork oak leaves and maritime pine needles based on LIF spectra - Lavrov, a; Utkin, a B.; Marques da Silva, J.; Vilar, Rui; Santos, N. M.; Alves, B. (Optics and Spectroscopy, 2012)
The aim of the present work was to develop a method for the remote assessment of the impact of fire and drought stress on Mediterranean forest species such as the cork oak (Quercus suber) and maritime pine (Pinus pinaster). The proposed method is based on laser induced fluorescence (LIF): chlorophyll fluo rescence is remotely excited by frequencydoubled YAG:Nd laser radiation pulses and collected and analyzed using a telescope and a gated high sensitivity spectrometer. The plant health criterion used is based on the I685 /I740 ratio value, calculated from the fluorescence spectra. The method was benchmarked by comparing the results achieved with those obtained by conventional, continuous excitation fluorometric method and water loss gravimetric measurements. The results obtained with both methods show a strong correlation between them and with the weightloss measurements, showing that the proposed method is suitable for fire and drought impact assessment on these two species
Keywords: Cork oak; laser induced fluorescence (LIF); maritime pine (voyant); water stress

Aperçu biologique du Platypus cylindrus (Fabricius, 1792) (Coleoptera, Curculionidae : Platypodinae) dans les galeries du bois de chêne-liège (Quercus suber L.) - Belhoucine, Latifa; Bouhraoua, Rachid Tarik; Dahane, Belkheir; PUJADE-VILLAR, JULI; Tarik Bouhraoua, Rachid (Orsis: organismes i sistemes, 2011)
The study of the biology of the insect Platypus cylindrus (Fabricius, 1792) in the galleries of the wood of cork oak was studied on the level of the national forest of M’Sila, littoral Oranian with semi arid climate. For that, 3 trees strongly infested by the pest were cut down between December 2007 and July 2008. The dissection of the 14 wood discs having a volume of 53 dm3 , enabled us to count 2920 individuals with an average density of 55 individuals/dm3 . At any time of the year, at least two stages of each population coexist together with fluctuating rates. The adult insects as well as the larvae are present throughout the period of experimentation. These last constitute the majority of the taken population (78%). The eggs and the nymphs, almost absent for wintry time appear in spring. Some morphological characteristics of larvae and eggs are set.
Keywords: Algeria.; biology; Cork oak; forest of M’Sila; Platypus cylindrus

Canopy cover influence on macrofungal richness and sporocarp production in montado ecosystems - Santos-Silva, C.; Gonçalves, A.; Louro, R. (Agroforestry Systems, 2011)
In this study we aimed to ﬁnd out how macrofungi richness and sporocarp production varies in relation to both canopy cover and proximity of crown projection area, in order to discuss strategies and point out management actions that ensure macrofungal communities sustainability in montado ecosystems. The sporocarp survey was conducted once every two weeks, from October to February, between 2007 and 2009 in two representative sites of the most common (cork and holm oak) open montado ecosystems in southern Portugal. Results showed that canopy cover strongly shaped macrofungal communities composition and yield. Denser canopy cover enhanced mycorrhizal richness and reduced saprotrophic yield. Furthermore, mycorrhizal richness and yield increased with tree proximity. Finally some forest management strategies are suggested in order to enhance macrofungal richness and productivity, in montado ecosystems.
Keywords: Cork oak; crown influence; Holm oak; macrofungal communities; Mediterranean ecosystem; montado; Portugal

Establishing grazing and grazing-excluded patches increases plant and invertebrate diversity in a Mediterranean oak woodland - Bugalho, Miguel N; Lecomte, Xavier; Gonçalves, Merícia; Caldeira, Maria C; Branco, Manuela (Forest Ecology and Management, 2011)
Grazing is a global, dominant land use affecting biodiversity and ecosystem processes. In Mediterranean ecosystems grazing is a major ecological and evolutionary driver but, surprisingly, there is little information on the use of grazing as a tool to manage biodiversity in these ecosystems. We conducted an experiment to assess if establishing grazing and small scale grazing-excluded areas would increase plant and invertebrate diversity in a Mediterranean evergreen oak woodland. Plant community traits were different between treatments. Biomass of herbs (176.7±18.3 gm−2 vs 100.4±10.6 gm−2) and litter (291.0±38.3 gm−2 vs 186.8±26.4 gm−2), as well as the total cover of legumes (0.83±0.05 vs 0.91±0.03) were higher, and the proportion of bare ground (0.83±0.05 vs 0.91±0.03) was lower, in ungrazed plots. There were no differences in the number of plant species between treatments. Some plant species and invertebrate taxa were recorded exclusively in grazed or ungrazed plots. Invertebrate detritivores and sap sucking insects were more abundant in ungrazed plots. Ant assemblages were functionally different between treatments: Honeydew-gatherer ants were associated with ungrazed and higher plant biomass plots, and seed-eaters as well as aggressive predator ant species were associated with grazed, open habitat, plots. Management practices that maintain grazing and small scale grazing-excluded areas can increase habitat heterogeneity and promote herbaceous plant and invertebrate diversity at the local level.
Keywords: Cork oak; Deer; Grazing management; Holm oak; Land-use; montados

Forty-four years of land use changes in a Sardinian cork oak agro-silvopastoral system: a qualitative analysis - Sedda, Luigi; Delogu, Giuseppe; Dettori, Sandro (The Open Forest Science Journal, 2011)
The island of Sardinia is the biggest producer of natural cork in Italy. In this study, cork oak cover change is investigated in a typical agro-silvopastoral system where the main activities are cereal fodder and wheat cultivation, sheep rearing and cork exploitation. The research method is based on the comparison of two land use maps produced by photo-interpretation of digitised aerial photographs taken in 1954 and 1998, combined with interviews with local farmers, field surveys, and data collected from literature, administrative documentation and decadal censuses (at council level). The results show that the cork oak woodland surface decreased (-29%). It was substituted by other forest, ploughed land, and mixed grassland and shrubland. Apart from the transformation of the cork oak woodland to other forest, other changes have happened probably because of an increase in agricultural and pastoral activities as described by the documental material available for the same area
Keywords: aerial photography classification; agro-forestry; Cork oak; forest cover; land use; multi-temporal analysis; Sardinia

Genetic divergence in Cork Oak based on cpDNA sequence data - Costa, Joana; Miguel, Célia; Almeida, Helena; Oliveira, Margarida M.; Matos, José a; Simões, Fernanda; Veloso, Manuela; Ricardo, Pinto C.; Paulo, Octávio S.; Batista, Dora (BMC Proceedings, 2011)
The following values have no corresponding Zotero field: periodical: BMC Proceedings issue: Suppl 7
Keywords: Cork oak; cpDNA (voyant); genetic diversity; Populations

Intraspecific variability of Pisolithus spp. as a response to changes in soil characteristics in a Moroccan cork oak plantation - Bakkali Yakhlef, Salah Eddine; Abourouh, Mohamed; Ducousso, Marc; Duponnois, Robin; Delaruelle, Christine; Mousain, Daniel (Mycology, 2011)
Soil characteristics may be an important factor in structuring fungal communities. We relate the above- and below-ground distribution of the ectomycorrhizal fungi (EMF) Pisolithus spp. to changes in soil chemistry in a Quercus suber plantation located in the Maâmora forest (Morocco). Intrageneric variability of 115 fruit bodies was studied, using morphological characterization, restriction fragment length polymorphism (RFLP) analyses and internal transcribed spacer (ITS) sequencing. Two Pisolithus spp. genotypes were identified: 97% of the fruit bodies represent Pisolithus arhizus; the remaining 3% correspond to Pisolithus species 4, as previously described by Martin et al. [New Phytologist 153 (2002) 345-357]. Multivariate analysis (PCA) showed that species structure was strongly correlated with soil characteristics. P. arhizus fruit bodies were frequently found in the Eastern part of the plot at low molasic clay, N and P contents, while Pisolithus species 4 were collected only in the Western part at the high molasic clay, N and P contents. To determine whether this change in fruit body structure was expressed at the belowground level, we used morphological and molecular techniques to characterize the Pisolithus ectomycorrhizas. Only ectomycorrhizas of P. arhizus were identified at the low P?N?molasic clay site and disappeared completely at the high P?N?red clay site, where no Pisolithus species 4 mycorrhizas were found. However, autocorrelation among soil parameters makes it difficult to isolate the effects of individual parameters. These results show the local-scale impact of natural spatial heterogeneity on an ectomycorrhizal fungal genus.
doi: 10.1080/21501203.2011.592155doi: 10.1080/21501203.2011.592155The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Cork oak; ITS sequencing; Morocco; Pisolithus; soil parameters

Method for evaluation of coarse cork oak root system by means of digital imaging - SUROVY, P; Ribeiro, N a.; BRASIL, F; Pereira, J S; OLIVEIRA, M R G (Agroforestry Systems, 2011)
Digital imaging is becoming a powerful tool for data storage and information retrieval. Image comparison and similarity evaluation has become part of the information market and it is today a common part of, for example, web search engines. The cork oak tree (Quercus suberL.), the dominant species of the ‘montado’ woodland system is, due to its cultural and socio-economic value, protected by law that prevents extensive destructive studies on an essential part of the tree—the root. Especially in the Mediterranean zone, where the water is the limiting growth factor, the root development studies are of signicant interest. In this work we present a method of using digital images for cork oak coarse root systems-evaluation by means of digital imaging. Acquired images of structural roots are processed automatically to prevent subjective decisions by the human observer. The performance of the method, its potential for semantic retrieval and similarity assessment is demonstrated, having as example eight young cork oak root systems, and critical issues for evaluation and conclusion-making, are discussed.
Keywords: coarse root system; Cork oak; digital image; image similarity

Temperature stress effects in Quercus suber leaf metabolism. - Chaves, Inês; Passarinho, José António P; Capitão, Cláudio; Chaves, Maria Manuela; Fevereiro, Pedro; Ricardo, Cândido P P (Journal of plant physiology, 2011)
Based on projections that climate changes are will intensify in the near future, it is important to understand how plants respond to climate. Consequently, we have been studying the effect of contrasting temperatures on leaf metabolism of Quercus suber, an important Mediterranean oak. Potted plants were grown under controlled conditions for 53 days at 28°C or 10°C. The accumulation of major soluble metabolites was analyzed by NMR. The relative levels of transcripts of genes encoding key enzymes of the shikimate and phenylpropanoid pathway (CS, PAL, CAD and ChS) were examined by means of quantitative, real-time RT-PCR. At 10°C, in the pre-existing leaves, the concentrations of sucrose, quercitol and catechin were higher, as were PAL and ChS transcripts. At 28°C, however, it was the concentration of quinic acid that was higher, as were the concentrations of CS and CAD transcripts. We conclude that contrasting temperatures greatly influence Q. suber metabolism and that a deeper analysis of the effects of more extreme temperatures is needed to understand the possible effects of temperature changes on Q. suber metabolism and physiology.
Keywords: Abiotic stress response; Cork oak; Phenol metabolism; Secondary metabolism

Variation of endophytic cork oak-associated fungal communities in relation to plant health and water stress - Linaldeddu, B. T.; Sirca, C.; Spano, D.; Franceschini, A. (Forest Pathology, 2011)
The main objective of this study was to obtain more comprehensive knowledge about the eﬀect of water stress on endophytic fungal communities in asymptomatic and declining cork oak trees. Six asymptomatic and six declining cork oak trees were randomly selected in a natural cork oak forest located in Sardinia, Italy. In February 2003, the soil around three asymptomatic and three declining trees was covered with a circular plastic ﬁlm to reduce rain water supply with the intention to induce water stress. The remaining six trees served as controls. Predawn xylematic water potential (PWP) was used as water status indicator and measured seasonally. Between July 2003 and June 2004, fungal endophytes were isolated every 2–4 months from twigs, branches and woody tissues. Signiﬁcant diﬀerences in PWP between covered and control trees were detected mainly in autumn. Gas exchange was greatest in asymptomatic control plants. All tissues were colonized by endophytic fungi. Nineteen fungal species were isolated from 1620 plant fragments. Biscogniauxia mediterranea was the most frequently isolated fungus. Its isolation frequency was signiﬁcantly higher in declining covered trees than in control trees (p < 0.05). Presence of this fungus in asymptomatic control trees was signiﬁcantly higher in winter than in summer. Water stress seems to reduce species diversity of the endophytic mycobiota in cork oak and to promote proliferation of some potentially pathogenic endophytes.
Keywords: Cork oak; fungal endophytes; gas exchange and water potential (voyant); water stress

Vessel size and number are contributors to define wood density in cork oak - Leal, Sofia; Sousa, Vicelina B; Knapic, Sofia; Louzada, José Luís; Pereira, Helena (European Journal of Forest Research, 2011)
Cork oak (Quercus suber L.) has a dense wood that allows high-quality uses. In the present work, we study the inﬂuence of vessel characteristics, measured through image analysis and optical microscopy, on wood density, measured using X-ray microdensitometry, on 40-year-old trees. Vessel area increases with cambial age (5403–33064 lm 2 ), while wood density decreases (1.229–0.836 g/cm 3 ). The number of vessels is relatively constant at 6 vessels/mm 2 , while vessel proportion in cross-section increases from 3.3% near the pith to 20.5% near the bark. In growth rings closest to the pith, with high wood density and low vessel area, the relationship between the two variables is linear (R 2 = -32.1%, P\0.01) but with increasing tree age and vessel size, the wood density remains rather constant, suggesting that decreases in density might compromise mechanical support of the tree at a stage when the increase in crosssectional area alone might not provide mechanical stability. Other anatomical characteristics not considered in this study, like large xylem rays that increase with cambial age, may be responsible for the constant density
Keywords: Cork oak; Quercus suber; vessels; wood anatomy; Wood density

THE CORK OAK FORESTS OF AQUITAINE: CONSERVATION VERSUS ECONOMIC REVIVAL - Puyo, Jean-Yves (SUD-OUEST EUROPEEN, 2010)
THE CORK OAK FORESTS OF AQUITAINE: CONSERVATION VERSUS ECONOMIC REVIVAL. The cork oak forests and plantations of Aquitaine were once the source of important communities of craftsmen devoted to cork processing. Two areas, le Marensin in the department of Landes and le Neracais in Lot-et-Garonne, have been enjoying renewed attention for the last decade. This paper aims at showing how these groves now become major stakes all the more since there ate so few of them left worldwide and are targeted by multiple projects aiming at either promoting the value of the landscape, sustaining biodiversity, or supporting traditional knowledge (from raising the cork to transforming it) as well as economic worth. Indeed, production has started anew on a few groves, after it came to a standstill more than forty years ago.
The following values have no corresponding Zotero field: pub-location: 5 ALLEES ANTONIO MACHADO, F-31058 TOULOUSE, FRANCE publisher: PRESSES UNIV MIRAIL
Keywords: Cork oak; Cork oak forests; HERTIAGE-MAKING PROCESS; MARENSIN; NERACAIS

Oak somatic and gametic embryos maturation is affected by charcoal and specific aminoacids mixture - Pintos, Beatriz; Manzanera, Jose a; Bueno, M. Angeles (Annals of Forest Science, 2010)
• Development of both somatic and gametic embryogenesis has many applications in clonal forestry and genetic improvement, for instance as mass-propagation of genetically improved plants and production of pure lines through doubled-haploid plant regeneration from gametic embryos. • The goal of this work was to improve growth, maturation and plantlet regeneration of cork oak (Quercus suber L.) embryos from both somatic and gametic origin. • Activated charcoal promoted a signiﬁcant increase in growth in terms of relative size and weight of both somatic and doubled-haploid embryos, as well as a more eﬃcient control of secondary somatic embryogenesis during development. A signiﬁcant interaction was also observed with amino acid nutrition. While some amino acids (i.e., glutamine, arginine or asparagine) did not show signiﬁcant diﬀerences with the controls, a mixture of these three amino acids or gamma amino butyric acid stimulated embryo growth. The highest survival rate during acclimation of plantlets from both somatic and doubled-haploid origin was obtained when the embryos had been previously cultured on basal medium with 3% sucrose and 1% activated charcoal for two months at 4 ◦ C and germinated on medium supplemented with 6-benzylaminopurine and indole-3-butyric acid. • We obtained more than 900 cork oak plantlets acclimated from several embryogenic lines, with a high survival rate, demonstrating that this methodology is applicable for large scale plantlet production. We also report the ﬁrst regeneration of doubled-haploid plantlets in cork oak.
Keywords: activated charcoal; amino acids; Cork oak; gametic embryo; plantlet acclimation

Presence of env-like sequences in Quercus suber retrotransposons - Carvalho, M.; Ribeiro, T.; Viegas, W.; Morais-Cecílio, L.; Rocheta, M. (Journal of Applied Genetics, 2010)
The main difference between LTR retrotransposons and retroviruses is the presence of theenvelope (env) gene in the latter, downstream of thepol gene. Theenv gene is involved in their infectious capacity. Here we report the presence ofenv-like sequences in the genome ofQuercus suber (cork oak), one of the most economically important Portuguese species. These gene sequences were isolated through DNA amplification betweenRNaseH conserved motifs and 3’ LTR, based on the structure ofcopia retrotransposons. Phylogenetic analysis revealed that almost all the clones isolated are clustered withCyclops-2, aTy3-gypsy element identified inPisum sativum, except one clustered withgypsy andcopia retroelements found in different species. This suggests the existence of a potential ancestral sequence of theenv gene, prior to the separation ofTy3-gypsy andTy1-copia retrotransposons. Additionally, the isolatedenv-like sequences showed 26–39% of homology withenv-like sequences characterized in viruses. The origin ofenv-like sequences in retrotransposons from host plant taxa is discussed.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: copia retroelements; Cork oak; envelope-like gene; retrotransposons; retrovirus

Factors affecting post-fire crown regeneration in cork oak (Quercus suber L.) trees - Catry, Filipe Xavier; Moreira, Francisco; Duarte, Inês; Acácio, Vanda (European Journal of Forest Research, 2009)
Cork oak (Quercus suber) forests are acknowledged for their biodiversity and economic (mainly cork production) values. WildWres are one of the main threats contributing to cork oak decline in the Mediterranean Basin, and one major question that managers face after Wre in cork oak stands is whether the burned trees should be coppiced or not. This decision can be based on the degree of expected crown regeneration assessed immediately after Wre. In this study we carried out a post-Wre assessment of the degree of crown recovery in 858 trees being exploited for cork production in southern Portugal, 1.5 years after a wildWre. Using logistic regression, we modelled good or poor crown recovery probability as a function of tree and stand variables. The main variables inXuencing the likelihood of good or poor crown regeneration were bark thickness, charring height, aspect and tree diameter. We also developed management models, including simpler but easier to measure variables, which had a lower predictive power but can be used to help managers to identify, immediately after Wre, trees that will likely show good crown regeneration, and trees that will likely die or show poor regeneration (and thus, potential candidates for trunk coppicing).
Keywords: Cork oak; crown regeneration; Forest management; wild w res; wildfires

Factors affecting post-fire crown regeneration in cork oak (Quercus suber L.) trees - Catry, Filipe Xavier; Moreira, Francisco; Duarte, Inês; Acácio, Vanda (European Journal of Forest Research, 2009)
Cork oak (Quercus suber) forests are acknowledged for their biodiversity and economic (mainly cork production) values. WildWres are one of the main threats contributing to cork oak decline in the Mediterranean Basin, and one major question that managers face after Wre in cork oak stands is whether the burned trees should be coppiced or not. This decision can be based on the degree of expected crown regeneration assessed immediately after Wre. In this study we carried out a post-Wre assessment of the degree of crown recovery in 858 trees being exploited for cork production in southern Portugal, 1.5 years after a wildWre. Using logistic regression, we modelled good or poor crown recovery probability as a function of tree and stand variables. The main variables inXuencing the likelihood of good or poor crown regeneration were bark thickness, charring height, aspect and tree diameter. We also developed management models, including simpler but easier to measure variables, which had a lower predictive power but can be used to help managers to identify, immediately after Wre, trees that will likely show good crown regeneration, and trees that will likely die or show poor regeneration (and thus, potential candidates for trunk coppicing).
Keywords: Cork oak; crown regeneration; Forest management; wild w res; wildfires

Field sampling of cork value before extraction in Portuguese ‘montados’ - Almeida, Alice M.; Tomé, Margarida (Agroforestry Systems, 2009)
The assessment of cork quality and the estimation of cork value are very important to forest landowners, for management purposes and for cork commercialisation. The Forest Producers Associations have been using a sampling scheme with the objective of estimating cork value (price per unit of weight, usually kg) before extraction, based on the sampling of individual trees along a zigzag transect that covers the entire stand. The sampling error is usually too high, but, from a practical standpoint, it is difﬁcult to increase the sampling intensity if it would imply an increase in sampling costs. The aim of this work was to propose, from data collected in six stands representative of the cork oak stands in Portugal, an alternative sampling methodology with a more efﬁcient precision/ cost ratio. Precision and costs of alternative sampling designs based on clusters of different sizes, complemented with analysis of the intracluster correlation coefﬁcient, were studied in order to propose the most adequate sampling strategy. Single-stage cluster sampling with clusters of 5–7 trees guarantees a reasonable sampling error (10–15%) and can be conducted without a large increase in cost.
Keywords: Cork oak; Cork quality; Cork thickness; Cork value; Intracluster correlation coefﬁcient; Single-stage cluster sampling

Field sampling of cork value before extraction in Portuguese ‘montados’ - Almeida, Alice M; Tomé, Margarida (Agroforestry Systems, 2009)
The assessment of cork quality and the estimation of cork value are very important to forest landowners, for management purposes and for cork commercialisation. The Forest Producers Associations have been using a sampling scheme with the objective of estimating cork value (price per unit of weight, usually kg) before extraction, based on the sampling of individual trees along a zigzag transect that covers the entire stand. The sampling error is usually too high, but, from a practical standpoint, it is difﬁcult to increase the sampling intensity if it would imply an increase in sampling costs. The aim of this work was to propose, from data collected in six stands representative of the cork oak stands in Portugal, an alternative sampling methodology with a more efﬁcient precision/ cost ratio. Precision and costs of alternative sampling designs based on clusters of different sizes, complemented with analysis of the intracluster correlation coefﬁcient, were studied in order to propose the most adequate sampling strategy. Single-stage cluster sampling with clusters of 5–7 trees guarantees a reasonable sampling error (10–15%) and can be conducted without a large increase in cost.
Keywords: Cork oak; Cork quality; Cork thickness; Cork value; Intracluster correlation coefﬁcient; Single-stage cluster sampling

Growth data from a field trial of Quercus suber plants regenerated from selected trees and from their half-sib progenies by somatic embryogenesis - Celestino, Cristina; Fernandez-Guijarro, B.; Hernández, Inmaculada; López Vela, Dolores; Carneros, Elena; Jiménez García, Jesús; Cardo, L.; Alegre, Jesús; Toribio, Mariano (Acta Horticulturae, 2009)
The development of reliable clonal propagation technologies is a requisite for performing Multi-Varietal Forestry (MVF). Somatic embryogenesis is considered the tissue culture based method more suitable for operational breeding of forest trees. Vegetative propagation is very difficult when tissues are taken from mature donors, making clonal propagation of selected trees almost impossible. We have been able to induce somatic embryogenesis in leaves taken from mature oak trees, including cork oak (Quercus suber). This important species of the Mediterranean ecosystem produces cork regularly, conferring to this species a significant economic value. In a previous paper we reported the establishment of a field trial to compare the growth of plants of somatic origin vs zygotic origin, and somatic plants from mature trees vs somatic plants from juvenile seedlings. For that purpose somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies by somatic embryogenesis. They were planted in the field together with acorn-derived plants of the same families. After the first growth period, seedlings of zygotic origin doubled the height of somatic seedlings, showing somatic plants of adult and juvenile origin similar growth. Here we provide data on height and diameter increases after two additional growth periods. In the second one, growth parameters of zygotic seedlings were also significantly higher than those of somatic ones, but there were not significant differences in height increase between seedlings and somatic plants of mature origin. In the third growth period, height and diameter increases of somatic seedlings cloned from the selected trees did not differ from those of zygotic seedlings, which were still higher than data from plants obtained from somatic embryos from the sexual progeny. Therefore, somatic seedlings from mature origin seem not to be influenced by a possible ageing effect, and plants from somatic embryos tend to minimize the initial advantage of plants from acorns.
Keywords: Cork oak; field establishment; forest improvement; rejuvenation; vegetative propagation; woody plant micropropagation

Growth data from a field trial of Quercus suber plants regenerated from selected trees and from their half-sib progenies by somatic embryogenesis - Celestino, Cristina; Fernández-Guijarro, B; Hernández, Inmaculada; López Vela, Dolores; Carneros, Elena; Jiménez García, Jesús; Cardo, L; Alegre, Jesús; Toribio, Mariano (Acta Horticulturae, 2009)
The development of reliable clonal propagation technologies is a requisite for performing Multi-Varietal Forestry (MVF). Somatic embryogenesis is considered the tissue culture based method more suitable for operational breeding of forest trees. Vegetative propagation is very difficult when tissues are taken from mature donors, making clonal propagation of selected trees almost impossible. We have been able to induce somatic embryogenesis in leaves taken from mature oak trees, including cork oak (Quercus suber). This important species of the Mediterranean ecosystem produces cork regularly, conferring to this species a significant economic value. In a previous paper we reported the establishment of a field trial to compare the growth of plants of somatic origin vs zygotic origin, and somatic plants from mature trees vs somatic plants from juvenile seedlings. For that purpose somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies by somatic embryogenesis. They were planted in the field together with acorn-derived plants of the same families. After the first growth period, seedlings of zygotic origin doubled the height of somatic seedlings, showing somatic plants of adult and juvenile origin similar growth. Here we provide data on height and diameter increases after two additional growth periods. In the second one, growth parameters of zygotic seedlings were also significantly higher than those of somatic ones, but there were not significant differences in height increase between seedlings and somatic plants of mature origin. In the third growth period, height and diameter increases of somatic seedlings cloned from the selected trees did not differ from those of zygotic seedlings, which were still higher than data from plants obtained from somatic embryos from the sexual progeny. Therefore, somatic seedlings from mature origin seem not to be influenced by a possible ageing effect, and plants from somatic embryos tend to minimize the initial advantage of plants from acorns.
Keywords: Cork oak; field establishment; forest improvement; rejuvenation; vegetative propagation; woody plant micropropagation

Implications of sheep and cattle Teline linifolia bush ingestion behaviour for managing the Maamora cork tree forest (Morocco) - Hracherrass, Ahmed; Berkat, Omar; De Montard, Francois-Xavier (CAHIERS AGRICULTURES, 2009)
The cork tree forest of Maamora near Rabat (Maroc) has suffered deep and increasing grazing pressure for 100 years. Dense understorey stands of Teline linifolia, a native, nitrogen fixing and vigorous legume shrub, would contribute to forest regeneration provided that it be proven to be a resource for sheep and cattle grazing. Autumn is a period with lower resources of grass and with no nitrogen fixing shrubs. In situ monthly measurements of sheep and cattle ingestion rates show a significant contribution of T. linifolia in both sheep (up to 24%) and cattle (up to 12%) total ingestion rates in autumn, due to its peculiar phenology along with the inadequacy of grass and other shrub resources at this time. The opportunity of planting Teline shrubs in the process of cork tree forest regeneration along with multi-purpose uses is described and discussed.
Keywords: Cattle; Cork oak; feeding preferences; Morocco; Regeneration; Sheep; Silvopastoral systems

Physiological responses of cork oak and holm oak to infection by fungal pathogens involved in oak decline - Linaldeddu, B. T.; Sirca, C.; Spano, D.; Franceschini, A. (Forest Pathology, 2009)
The aim of this research was to study the changes in net photosynthesis and stomatal conductance values in 3-year-old cork oak and holm oak seedlings growing in natural conditions and inoculated with Apiognomonia quercina, Biscogniauxia mediterranea, Botryosphaeria corticola and Pleurophoma cava. Throughout the 4-month experimental period, the evolution of visual external symptoms and the values of physiological variables were periodically recorded. All pathogens caused stem lesions around the infection point; however, the lesions caused by B. corticola were longer in both oak species. On cork oak seedlings, all pathogens induced a signiﬁcant and gradual reduction in net photosynthesis and stomatal conductance values, whereas other physiological disturbances were induced only by B. corticola infections on holm oak seedlings.
Keywords: Cork oak; fungal pathogens; Holm oak; physiological responses (voyant); seedlings

Proteomic analysis from haploid and diploid embryos of Quercus suber L. identifies qualitative and quantitative differential expression patterns. - Gómez, Aranzazu; López, Juan Antonio; Pintos, Beatriz; Camafeita, Emilio; Bueno, Ma Angeles (Proteomics, 2009)
Quercus suber L. is a Mediterranean forest species with ecological, social and economic value. Clonal propagation of Q. suber elite trees has been successfully obtained from in vitro-derived somatic and gametic embryos. These clonal lines play a main role in breeding and genetic studies of Q. suber. To aid in unravelling diverse genetic and biological unknowns, a proteomic approach is proposed. The proteomic analysis of Q. suber somatic and gametic in vitro culture-derived embryos, based on DIGE and MALDI-MS, has produced for the first time proteomic data on this species. Seventeen differentially expressed proteins have been identified which display significantly altered levels between gametic and somatic embryos. These proteins are involved in a variety of cellular processes, most of which had been neither previously associated with embryo development nor identified in the genus Quercus. Some of these proteins are involved in stress and pollen development and others play a role in the metabolism of tannins and phenylpropanoids, which represent two of the major pathways for the synthesis of cork chemical components. Furthermore, the augmented expression levels found for specific proteins are probably related to the homozygous state of a doubled-haploid sample. Proteins involved in synthesis of cork components can be detected at such early stages of development, showing the potential of the method to be useful in searching for biomarkers related to cork quality.
Keywords: cluster analysis; Cork oak; Diploidy; Electrophoresis; Embryonic Development; flow cytometry; Gametic embryogenesis; Gel; Haploid and diploid embryos; Haploidy; Plant Proteins; Plant Proteins: analysis; Plant Proteins: biosynthesis; Plant Proteins: genetics; Plant proteomics; Ploidies; Ploidy level; Principal component analysis; Proteomics; Proteomics: methods; Quercus; Quercus suber L.; Quercus: chemistry; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Seeds: genetics; Seeds: metabolism; Two-Dimensional; Up-Regulation

Economic implications of different cork oak forest management systems - Pinheiro, A. C.; Ribeiro, N. A. (2008)
The agro-silvopastoral system “montado” dominates the landscape of the south-western Iberian Peninsula, occupies approximately 3.1 million hectares of woodland in Spain and 1.2 million hectares in Portugal. The forest system “montado” is mostly dominated by Mediterranean evergreen oaks such as cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia). The “montado” production system management aims the maintenance of a balanced sustainable land use to cope with the Mediterranean climate variability. One important issue in cork oak forests is the control shrub growth in order to prevent forest fire hazard, which is of high risk in Mediterranean climate. The two most common ways of controlling the shrub component is by mechanical destruction with soil disking (that implicates soil mobilization) or by shrub cutting (that is done with minimum impact on soil). The two referred techniques have different costs and different impacts on cork production and other goods and services (multifunctionality) of cork oak forests. In this paper, the two shrub control systems are compared and the results show that, although soil disking is more profitable than shrub cutting, the results are reversed, if one considers the carbon sequestration. This means that besides the great economic sustainability of cork oak dependence on the price of cork, the profitability of different shrub control methods depend also on the way society valuates other goods and services provided by cork oak forest
The following values have no corresponding Zotero field: secondary-title: International Journal of … periodical: International Journal of … electronic-resource-num: 10.1504/IJSSOC.2008.022571
Keywords: Cork oak; NPV; Sustainability; woodlands

Economic implications of different cork oak forest management systems - Pinheiro, A C; Ribeiro, N A (International Journal of …, 2008)
The agro-silvopastoral system “montado” dominates the landscape of the south-western Iberian Peninsula, occupies approximately 3.1 million hectares of woodland in Spain and 1.2 million hectares in Portugal. The forest system “montado” is mostly dominated by Mediterranean evergreen oaks such as cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia). The “montado” production system management aims the maintenance of a balanced sustainable land use to cope with the Mediterranean climate variability. One important issue in cork oak forests is the control shrub growth in order to prevent forest fire hazard, which is of high risk in Mediterranean climate. The two most common ways of controlling the shrub component is by mechanical destruction with soil disking (that implicates soil mobilization) or by shrub cutting (that is done with minimum impact on soil). The two referred techniques have different costs and different impacts on cork production and other goods and services (multifunctionality) of cork oak forests. In this paper, the two shrub control systems are compared and the results show that, although soil disking is more profitable than shrub cutting, the results are reversed, if one considers the carbon sequestration. This means that besides the great economic sustainability of cork oak dependence on the price of cork, the profitability of different shrub control methods depend also on the way society valuates other goods and services provided by cork oak forest
Keywords: Cork oak; NPV; Sustainability; woodlands

Effects of treeshelters and polyethylene mulch sheets on survival and growth of cork oak (Quercus suber L.) seedlings planted in northwestern Tunisia - Chaar, Hatem; Mechergui, Taher; Khouaja, Ali; Abid, Habib (Forest Ecology and Management, 2008)
Success of plantation establishment depends on the ability of seedlings to withstand animal browsing and competition from vegetation. This study in northwestern Tunisia examined the inﬂuence of browsing protection and vegetation control on seedling mortality, diameter, and height growth components of an evergreen sclerophyllous oak species, cork oak (Quercus suber L.) for the ﬁrst 2 years after planting (2005 and 2006). Browsing protection was controlled by varying both treeshelter type (non-vented, vented, and control) and height (1.2-m and 1.8-m tall). Competing vegetation was controlled through increasing sizes of square-shaped black polyethylene mulch sheets: 0 m, 0.7 m, 1 m and 1.3 m large. Seedling mortality rate was relatively low during the ﬁrst year (9%) and was not affected by any of the studied factors. During the following year, mortality was lower for seedlings in both types (non-vented and vented) of 1.2-m tall treeshelters than for unsheltered ones. Mortality was only slightly higher for 1.8-m tall shelters than for 1.2-m shelters. Compared to unsheltered seedlings, basal diameter was reduced during both seasons for seedlings inside non-vented treeshelters (1.2-m and 1.8-m tall), whereas for vented shelters it was reduced during the ﬁrst year and then increased during the second year. Height growth was positively affected by tree shelters during both years. Seedlings inside non-vented 1.8-m tall shelters were the tallest having an average height of up to 140 cm at the end of the second year, while the unsheltered seedlings had only an average height of up to 42 cm. The greater height of the sheltered seedlings was attributed to the increase of: (1) the number of shoot ﬂushes yearly established on the main stem (up to three), and (2) the length of all the growth units produced during each ﬂush. Seedlings inside vented shelters had balanced growth with a low proportion of seedlings unable to support themselves without a stake (7%). However, non-vented shelters had unbalanced height and diameter growths resulting in both a higher height-to-diameter ratio and in a higher proportion of seedlings having stability problems (47%). Polyethylene mulch sheets did not affect early survival, seedling basal diameter, or number of shoot ﬂushes established yearly, but did slightly improve seedling height at the end of the second season, mostly due to the signiﬁcant improvement in shoot elongation of the ﬁrst ﬂush. Results suggest that both 1.8 m treeshelters and plastic mulches may enhance the growth of cork oak seedlings planted on harsh sites in northwestern Tunisia.
Keywords: Cork oak; Growth; herbivory; plantation; Polyethylene sheets; Quercus suber L.; Treeshelter

Elevated atmospheric CO2 does not modify osmotic adjustment to light and drought in the Mediterranean oak" Quercus suber L." - Aranda, I.; Simón, J. Puértolas (Investigación agraria. Sistemas y recursos forestales, 2008)
The current ongoing increase in the atmospheric CO2 concentration is an unquestionable fact. Thus, plants are bound to live in a more enriched CO2 world in a not far-off future. In this new framework, regeneration of forest tree species may be modified as a consequence of the change in the current patterns of seedling response to other environmental resources, such as water or light. We studied the impact of an elevated CO2 concentration on the interaction of drought and light upon the water relations of cork oak (Quercus suber L.) seedlings. In a complete factorial design of contrasting light (HL vs LL), water (WW vs S) and CO2 levels (800 ppm vs 370 ppm), we analysed the influence of each factor and its interaction in the modification of different leaf water parameters in potted seedlings after a 6 months experimental period. These parameters were derived from the construction, with leaf materials, of the P-V curves: osmotic potential at full turgor (Ψπ100), osmotic potential at zero turgor (Ψπ0), modulus of elasticity at full turgor (εmax), and the ratio dry/turgor weight (DW/TW). Doubling of the CO2 levels over the current concentration (380 ppm) did not change any of the studied leaf water parameters, while light and water availabilities had a significant influence. This result does not exclude changes in other basic physiological parameters that could modify the pattern of cork oak regeneration responding to a CO2 enriched atmosphere in the future, and under climatic conditions different to the current ones
Keywords: CO2 enrichment; Cork oak; PV curves; shade; Water availability

Elevated atmospheric CO2 does not modify osmotic adjustment to light and drought in the Mediterranean oak" Quercus suber L." - Aranda, I; Simón, J Puértolas (Investigación agraria. Sistemas y recursos forestales, 2008)
The current ongoing increase in the atmospheric CO2 concentration is an unquestionable fact. Thus, plants are bound to live in a more enriched CO2 world in a not far-off future. In this new framework, regeneration of forest tree species may be modified as a consequence of the change in the current patterns of seedling response to other environmental resources, such as water or light. We studied the impact of an elevated CO2 concentration on the interaction of drought and light upon the water relations of cork oak (Quercus suber L.) seedlings. In a complete factorial design of contrasting light (HL vs LL), water (WW vs S) and CO2 levels (800 ppm vs 370 ppm), we analysed the influence of each factor and its interaction in the modification of different leaf water parameters in potted seedlings after a 6 months experimental period. These parameters were derived from the construction, with leaf materials, of the P-V curves: osmotic potential at full turgor (Ψπ100), osmotic potential at zero turgor (Ψπ0), modulus of elasticity at full turgor (εmax), and the ratio dry/turgor weight (DW/TW). Doubling of the CO2 levels over the current concentration (380 ppm) did not change any of the studied leaf water parameters, while light and water availabilities had a significant influence. This result does not exclude changes in other basic physiological parameters that could modify the pattern of cork oak regeneration responding to a CO2 enriched atmosphere in the future, and under climatic conditions different to the current ones
Keywords: CO2 enrichment; Cork oak; PV curves; shade; Water availability

Fungi of Raffaelea genus ( Ascomycota : Ophiostomatales ) associated to Platypus Cylindrus ( Coleoptera : Platypodidae ) in Portugal - Inácio, Maria Lurdes; Henriques, Joana; Lima, Arlindo; Sousa, Edmundo (Revista de Ciências Agrárias, 2008)
In the study of the fungi associated to Platypus cylindrus, several fungi were isolated from the insect and its galleries in cork oak, among which three species of Raffaelea. Morphological and cultural characteristics, sensitivity to cycloheximide and genetic variability had been evaluated in a set of isolates of this genus. On this basis R. ambrosiae and R. montetyi were identified and a third taxon segregated witch differs in morphological and molecular characteristics from the previous ones. In this work we present and discuss the parameters that allow the identification of specimens of the three taxa. The role that those ambrosia fungi can have in the cork oak decline is also discussed taking into account that Ophiostomatales fungi are pathogens of great importance in trees, namely in species of the genus Quercus.
Keywords: Ambrosia beetle; ambrosia fun- gi; Cork oak; decline

Influence of the soil water holding capacity on the potential distribution of forest species. A case study: the potential distribution of cork oak (Quercus suber L.) in central-western Spain - Jovellar Lacambra, Luis Carlos; Blanco Andray, Alfredo; Santos Francés, Fernando (European Journal of Forest Research, 2008)
This study reports a parametric approach to the climatic and edaphoclimatic potential distribution of the cork oak (Quercus suber L.) in central-western Spain together with an analysis of the in Xuence of the maximum soil water holding capacity (WHC) on such potential distribution. To these ends, we employed 12 climatic and 2 edaphoclimatic parameters of eco-physiological in Xuence derived from the current distribution of cork oaks. The climatic and edaphoclimatic parameters elaborated for two extreme WHC values (50 and 250 mm) are calculated for the whole study area and are mapped by means of a digital elevation model and a geographic information system. The results point to an important climatic potential area for high soil WHC values but there is also a remarkable dependence on this latter parameter, mainly in the Duero basin, since the limits of the climatic potential area are reduced strongly as WHC decreases. We deduce certain other conclusions as regards the importance of this variable in the potential distribution of species and in forestation and reforestation projects using this species.
Keywords: Cork oak; edaphoclimatic parameters; Potential distribution; Quercus suber; soil water holding capacity

Interactive responses of Quercus suber L. seedlings to light and mild water stress: effects on morphology and gas exchange traits - Puértolas, J; Pardos, M; Jiménez, M D (Annals of Forest Science, 2008)
• The combined eﬀect of water stress and light on seedlings of forest species is a key factor to determine the best silvicultural and aﬀorestation practices in the Mediterranean area. • The aims of this work was (1) to determine the optimal light level for the early development of cork oak seedlings under mild water stress and (2) to test if the combined eﬀect of water stress and light followed the trade-oﬀ, the facilitation or the orthogonal hypothesis. • Shade reduced instantaneous photosynthetic rates and water use eﬃciency in cork oak. However, seedlings grown under moderate shade (15% of full sunlight) were capable to accumulate similar amount of biomass than those grown under more illuminated environments by increasing their speciﬁc leaf area. Absolute diﬀerences in net photosynthesis between light treatments were higher in well watered than in water stressed seedlings. However, the impact of both factors on overall growth was orthogonal. • We concluded that cork oak development is impaired under deep shade (5% of full sunlight) but it can be optimal under moderate shade (15% of full sunlight) even under moderate water stress. Implications of these patterns on regeneration, cultivation and aﬀorestation of cork oak are discussed.
Keywords: Cork oak; foliar anatomy; photosynthesis rate; shade acclimation; water use effciency

Interactive responses of Quercus suber L. seedlings to light and mild water stress: effects on morphology and gas exchange traits - Puértolas, J.; Pardos, M.; Jiménez, M. D. (Annals of Forest Science, 2008)
• The combined eﬀect of water stress and light on seedlings of forest species is a key factor to determine the best silvicultural and aﬀorestation practices in the Mediterranean area. • The aims of this work was (1) to determine the optimal light level for the early development of cork oak seedlings under mild water stress and (2) to test if the combined eﬀect of water stress and light followed the trade-oﬀ, the facilitation or the orthogonal hypothesis. • Shade reduced instantaneous photosynthetic rates and water use eﬃciency in cork oak. However, seedlings grown under moderate shade (15% of full sunlight) were capable to accumulate similar amount of biomass than those grown under more illuminated environments by increasing their speciﬁc leaf area. Absolute diﬀerences in net photosynthesis between light treatments were higher in well watered than in water stressed seedlings. However, the impact of both factors on overall growth was orthogonal. • We concluded that cork oak development is impaired under deep shade (5% of full sunlight) but it can be optimal under moderate shade (15% of full sunlight) even under moderate water stress. Implications of these patterns on regeneration, cultivation and aﬀorestation of cork oak are discussed.
Keywords: Cork oak; foliar anatomy; photosynthesis rate; shade acclimation; water use effciency

La renta ambiental de los bosques - Campos Palacín, P.; Caparrós Gass, A. (ARBOR Ciencia, Pensamiento y Cultura, 2008)
The objective of this paper is to show the measurement of the environmental income from two private Spanish forests, the Cork Oak Woodlands of the Alcornocales Natural Park (Cádiz and Málaga) and the Scotch Pine Forest of the Sierra de Guadarrama (Madrid and Segovia). We also contribute to the technical and political debate on governmental regulations of forest environmental accounting in European Union. We have measured the environmental goods and services consumed by private landowners and public visitors through the contingent valuation technique. We have estimated the value of mushrooms gathering by public visitors in the Scotch Pine Forests of the Sierra de Guadarrama taking the price and harvest from the mushroom market in Pinar Grande (Soria). The value for carbon estimated accounts for the avoided damage of the greenhouse effect mitigation due to the sequestration of the atmospheric carbon dioxide. The environmental valuations show that the private environmental profitability rates in the Alcornocales Natural Park and in the Sierra de Guadarrama are 2.13 % and 3.43 %, in relation to their corresponding land market prices. We have estimated that the total net values added are 1.63 and 3.28 times higher than its corresponding conventional net values added in the Alcornocales Natural Park and in the Sierra de Guadarrama.
Keywords: consumer surplus; Cork oak; Exchange value; Hicksian income; joint production; public expenditure; Scotch pine

La renta ambiental de los bosques - CAMPOS PALACIN, P; CAPARROS GASS, A (ARBOR Ciencia, Pensamiento y Cultura, 2008)
The objective of this paper is to show the measurement of the environmental income from two private Spanish forests, the Cork Oak Woodlands of the Alcornocales Natural Park (Cádiz and Málaga) and the Scotch Pine Forest of the Sierra de Guadarrama (Madrid and Segovia). We also contribute to the technical and political debate on governmental regulations of forest environmental accounting in European Union. We have measured the environmental goods and services consumed by private landowners and public visitors through the contingent valuation technique. We have estimated the value of mushrooms gathering by public visitors in the Scotch Pine Forests of the Sierra de Guadarrama taking the price and harvest from the mushroom market in Pinar Grande (Soria). The value for carbon estimated accounts for the avoided damage of the greenhouse effect mitigation due to the sequestration of the atmospheric carbon dioxide. The environmental valuations show that the private environmental profitability rates in the Alcornocales Natural Park and in the Sierra de Guadarrama are 2.13 % and 3.43 %, in relation to their corresponding land market prices. We have estimated that the total net values added are 1.63 and 3.28 times higher than its corresponding conventional net values added in the Alcornocales Natural Park and in the Sierra de Guadarrama.
Keywords: consumer surplus; Cork oak; Exchange value; Hicksian income; joint production; public expenditure; Scotch pine

A spatial distribution model of cork oak (Quercus suber) in southwestern Spain: A suitable tool for reforestation - Hidalgo, P J; Marín, J M; Quijada, J; Moreira, J M (Forest Ecology and Management, 2008)
Cork oak (Quercus suber) is an evergreen tree characterized by a thick bark, which grows in Mediterranean schlerophyllous forests. It is most prevalent in the southwestern Iberian Peninsula. Despite the potential of the province of Huelva (southwestern Spain) to maintain mature forests of cork oak, the tree has been severely depleted and most forests have either disappeared or are seriously threatened. This paper presents a spatial distribution model of cork oak for the province of Huelva with a view to determining the optimal areas for reforestation. The model draws on all available digital cartographic information with respect to cork oak distribution: topographic data (altitude, slope and orientation) were obtained from a Digital Terrain Model (20 m scale); rainfall, temperature and PET models were based on data collected from a network of meteorological stations; litologic data derive from the litologic map of Huelva (1:100,000). The result of this work is a mesh of points at a resolution of 100 m, sufﬁcient to meet the needs of any kind of reforestation or management programmes in the area studied. Each point of this mesh contains the corresponding values for bioclimatic, topographic and litologic variables in a georeferenced data matrix. The independent variables responsible for cork oak distribution (binary dependent variables) were then identiﬁed by means of binary logistic regression analysis. North-facing slopes, abundant annual rainfall and litology were the main explaining variables. The spatial distribution model was produced by applying the formula obtained to spatial analysis software. This model is proposed as a basis for future reforestation plans, especially in those areas most affected by forest ﬁres.
Keywords: binary logistic regression; climatic modeling; Cork oak; Quercus suber; Reforestation; spatial analysis

Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.
Keywords: canker disease; Cork oak; Diplodia corticola; phytotoxic metabolites; Quercus suber L.

Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.
Keywords: canker disease; Cork oak; Diplodia corticola; phytotoxic metabolites; Quercus suber L.

Estimation of white grub damage (Coleoptera : Scarabaeoidea) in cork oak (Quercus suber L.) regeneration parcels of the Mamora forest (Morocco) and search for biological control using sex pheromones. - Ghaioule, Driss; Lumaret, Jean-Pierre; Rochat, Didier; Maatouf, Noureddine; Niogret, Jerome (ANNALES DE LA SOCIETE ENTOMOLOGIQUE DE FRANCE, 2007)
During the last decades, the cork oak restoration in the Mamora forest (Morocco) was faced with massive root attacks of seedling plantations by white grubs (Coleoptera: Scarabaeoidea). In most cases, the success of the restoration reached only 12%. Sphodroxia maroccana Ley (Melolonthidae) can be considered as the main pest in the restoration parcels. Some traits of the biology of this species are specified, despite shortcomings in the knowledge of the precise period of male emergence with regard to females, the longevity of adults and the sex-ratio. Summer drought, a season without white grub activity, is another main cause of mortality of young plantations. During the first year after plantation in experimental parcels, the cumulated mortality due to these two factors ranged between 41 and 68% according to the blocks in the parcels. The mortality associated with S. maroccana larvae ranged between 24 and 43%, with a distribution of infestation depending on density of young plants. Solid phase micro-extraction used to sample volatiles from the headspace of S. maroccana females allowed to isolate resorcinol (1,3-benzenediol) as presumed female sex pheromone. The role of this molecule has to be demonstrated.
Keywords: 1-3-benzenediol; biological control; Cork oak; damage; Morocco; pheromone; resorcinol; Restoration; Scarabaeoidea; white grubs

Estimation of white grub damage (Coleoptera : Scarabaeoidea) in cork oak (Quercus suber L.) regeneration parcels of the Mamora forest (Morocco) and search for biological control using sex pheromones. - Ghaioule, Driss; Lumaret, Jean-Pierre; Rochat, Didier; Maatouf, Noureddine; Niogret, Jerome (ANNALES DE LA SOCIETE ENTOMOLOGIQUE DE FRANCE, 2007)
During the last decades, the cork oak restoration in the Mamora forest (Morocco) was faced with massive root attacks of seedling plantations by white grubs (Coleoptera: Scarabaeoidea). In most cases, the success of the restoration reached only 12%. Sphodroxia maroccana Ley (Melolonthidae) can be considered as the main pest in the restoration parcels. Some traits of the biology of this species are specified, despite shortcomings in the knowledge of the precise period of male emergence with regard to females, the longevity of adults and the sex-ratio. Summer drought, a season without white grub activity, is another main cause of mortality of young plantations. During the first year after plantation in experimental parcels, the cumulated mortality due to these two factors ranged between 41 and 68% according to the blocks in the parcels. The mortality associated with S. maroccana larvae ranged between 24 and 43%, with a distribution of infestation depending on density of young plants. Solid phase micro-extraction used to sample volatiles from the headspace of S. maroccana females allowed to isolate resorcinol (1,3-benzenediol) as presumed female sex pheromone. The role of this molecule has to be demonstrated.
The following values have no corresponding Zotero field: pub-location: 45 RUE BUFFON, 75005 PARIS, FRANCE publisher: SOC ENTOMOLOGIQUE FRANCE
Keywords: 1-3-benzenediol; biological control; Cork oak; damage; Morocco; pheromone; resorcinol; Restoration; Scarabaeoidea; white grubs

First data from a field trial of Quercus suber plants regenerated from mature selected trees and from their half-sib progenies by somatic embryogenesis - CELESTINO, C; HERNÁNDEZ, I; Lopez-Vela, D; CARNEROS, E; ALEGRE, J; TORIBIO, M; Fernández-Guijarro, B; Cardo, L (Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants, 2007)
Somatic embryogenesis is considered as the most suitable current regeneration technique for the conservation and genetic improvement of tree species. The ability to induce somatic embryogenesis in leaves from mature trees gives the possibility to compare the performance of the parent trees and their progenies at the same age and place of test. Somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies. They were planted in the field conjointly with zygotic seedlings of these families, to test the comparisons somatic vs. zygotic origin and somatic from mature trees vs. somatic from juvenile seedlings. The effect of genotype and kind of progeny will be studied in a complete factorial design; therefore the field trial comprised 15 treatments arranged in five completely randomised blocks. Each experimental unit included three plants that were distributed following a row and column pattern. Fist survival and height data after six and twelve months of establishment are provided. All plants from seeds survived while almost the half of somatic seedlings died after the winter and they were replaced. Almost 70% of these plants survived after the following summer. There were no differences between somatic seedlings of mature or juvenile origin. Zygotic seedlings doubled the height of the somatic ones after one year in the field, and within these plants those of mature origin grew slightly more than those of juvenile source. Differences due to genotype and family effects were noticeable. No apparent morphological alterations were detected among the three kinds of tested progenies.
Keywords: Cork oak; field establishment; rejuvenation; Somatic embryogenesis; woody plant micro-propagation

First data from a field trial of Quercus suber plants regenerated from mature selected trees and from their half-sib progenies by somatic embryogenesis - Celestino, C.; Hernández, I.; Lopez-Vela, D.; Carneros, E.; Alegre, J.; Toribio, M.; Fernandez-Guijarro, B.; Cardo, L. (Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants, 2007)
Somatic embryogenesis is considered as the most suitable current regeneration technique for the conservation and genetic improvement of tree species. The ability to induce somatic embryogenesis in leaves from mature trees gives the possibility to compare the performance of the parent trees and their progenies at the same age and place of test. Somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies. They were planted in the field conjointly with zygotic seedlings of these families, to test the comparisons somatic vs. zygotic origin and somatic from mature trees vs. somatic from juvenile seedlings. The effect of genotype and kind of progeny will be studied in a complete factorial design; therefore the field trial comprised 15 treatments arranged in five completely randomised blocks. Each experimental unit included three plants that were distributed following a row and column pattern. Fist survival and height data after six and twelve months of establishment are provided. All plants from seeds survived while almost the half of somatic seedlings died after the winter and they were replaced. Almost 70% of these plants survived after the following summer. There were no differences between somatic seedlings of mature or juvenile origin. Zygotic seedlings doubled the height of the somatic ones after one year in the field, and within these plants those of mature origin grew slightly more than those of juvenile source. Differences due to genotype and family effects were noticeable. No apparent morphological alterations were detected among the three kinds of tested progenies.
The following values have no corresponding Zotero field: periodical: Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants issue: 748 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: Cork oak; field establishment; rejuvenation; Somatic embryogenesis; woody plant micro-propagation

First Report of Canker Disease Caused by Botryosphaeria parva on Cork Oak Trees in Italy - Linaldeddu, B. T.; Franceschini, A.; Luque, J.; Phillips, A. J. L. (Plant Disease, 2007)
A survey was carried out in the spring of 2003 to study the fungi associated with declining trees in a cork oak (Quercus suber L.) forest located in Sassari Province, Sardinia, Italy (40°52?N, 9°01?E) at an altitude of 150 m (above sea level). Several isolates obtained from live twigs and branches showing sunken necrotic bark lesions were identified as Fusicoccum parvum Pennycook EF1-α: 100%). Representative sequences of both regions were deposited at GenBank (ITS: Accession No. DQ487157; EF1-α: Accession No. DQ487158). Pathogenicity tests were carried out on seven 2-year-old cork oak seedlings maintained in a greenhouse at 14 to 26°C with the B. parva strain CBS 119937 obtained in this study. A mycelial plug (3 to 4 mm2) taken from the margin of an actively growing colony on PDA was put in a shallow wound made by a scalpel on the basal part of the stem of each seedling. Sterile PDA plugs were placed into similar wounds on three control seedlings. The inoculation points were wrapped in Parafilm to retain moisture for 1 week. After 4 weeks, all seedlings inoculated with B. parva died and showed a collapse of the stem cortical tissues associated with dark brown discolorations and vascular necrosis measuring 10.9 ± 0.4 cm. No symptoms were visible in the control seedlings. The pathogen was reisolated from all the inoculated seedlings, thus fulfilling Koch's postulates. The results confirm the virulence of this fungus and point to its possible involvement in the aetiology of cork oak decline. B. parva is a cosmopolitan, plurivorous pathogen causing disease in several hosts of economic importance, such as grapevine (3), kiwi (2), and Eucalyptus spp. trees (1). To our knowledge, this is the first report of B. parva causing canker disease on cork oak trees. References: (1) A. Gezahgne et al. S. Afr. J. Bot. 70:241, 2004. (2) S. R. Pennycook and G. J. Samuels. Mycotaxon 24:445, 1985. (3) A. J. L. Phillips. Phytopathol. Mediterr. 41:3, 2002. (4) B. Slippers et al. Mycologia 96:83, 2004.
doi: 10.1094/PDIS-91-3-0324Adoi: 10.1094/PDIS-91-3-0324AThe following values have no corresponding Zotero field: publisher: Scientific Societies
Keywords: canker disease; Cork oak; Italy (voyant)

Gall wasps and their parasitoids in cork oak fragmented forests - CHUST, GUILLEM; GARBIN, LUCAS; PUJADE-VILLAR, JULI (Ecological Entomology, 2007)
Abstract 1. This paper explores the potential effects of host-plant fragmentation on cork oak gall wasp populations (Cynipidae, Hymenoptera) and on their predators, lethal inquilines, and parasitoids. To address this objective, galls were collected across a gradient of cork oak (Quercus suber) forest fragmentation in the East Pyrenees (Albera, Spain), and they were incubated to obtain the parasitism rates. 2. Two hypotheses were tested: (1) Host-plant fragmentation may induce a decline in gall wasp populations because of area and isolation effects on local extinction and dispersal; as a consequence of that, parasitoids may decline even more strongly in fragmented habitats than their prey. (2) Host-plant fragmentation may cause a decline in gall wasp parasitoid populations that, in turn, can lead to an ecological release in their prey populations. 3. Among the eight cork oak gall wasps sampled in the study area of Albera, the gall abundances of three species (Callirhytis glandium, Callirhytis rufescens, and Andricus hispanicus) were significantly related to forest fragmentation. The overall abundance of gall wasps was affected by a radius of ≈ 890 m surrounding landscape, presenting constant abundances with forest loss until forest cover is reduced at ≈ 40%; below that value the abundance increased rapidly. Three inquilines and 23 parasitoids species were recorded after gall incubation. In 25 cases, species of inquilines and parasitoids were newly recorded for the corresponding host in the Iberian peninsula. 4. Although the overall parasitism rate was high (1.1), it was uncorrelated with fragmentation and with overall cynipid abundance. These results indicate that host-plant fragmentation was correlated with higher abundance of gall wasps, whereas the parasitism rate could not explain this hyper-abundance in small forest fragments.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cork oak; fragmentation; gall wasp; parasitism rate; parasitoid; Pyrenees; Quercus suber

Gall wasps and their parasitoids in cork oak fragmented forests - CHUST, GUILLEM; GARBIN, LUCAS; PUJADE-VILLAR, JULI (Ecological Entomology, 2007)
Abstract 1. This paper explores the potential effects of host-plant fragmentation on cork oak gall wasp populations (Cynipidae, Hymenoptera) and on their predators, lethal inquilines, and parasitoids. To address this objective, galls were collected across a gradient of cork oak (Quercus suber) forest fragmentation in the East Pyrenees (Albera, Spain), and they were incubated to obtain the parasitism rates. 2. Two hypotheses were tested: (1) Host-plant fragmentation may induce a decline in gall wasp populations because of area and isolation effects on local extinction and dispersal; as a consequence of that, parasitoids may decline even more strongly in fragmented habitats than their prey. (2) Host-plant fragmentation may cause a decline in gall wasp parasitoid populations that, in turn, can lead to an ecological release in their prey populations. 3. Among the eight cork oak gall wasps sampled in the study area of Albera, the gall abundances of three species (Callirhytis glandium, Callirhytis rufescens, and Andricus hispanicus) were significantly related to forest fragmentation. The overall abundance of gall wasps was affected by a radius of ≈ 890 m surrounding landscape, presenting constant abundances with forest loss until forest cover is reduced at ≈ 40%; below that value the abundance increased rapidly. Three inquilines and 23 parasitoids species were recorded after gall incubation. In 25 cases, species of inquilines and parasitoids were newly recorded for the corresponding host in the Iberian peninsula. 4. Although the overall parasitism rate was high (1.1), it was uncorrelated with fragmentation and with overall cynipid abundance. These results indicate that host-plant fragmentation was correlated with higher abundance of gall wasps, whereas the parasitism rate could not explain this hyper-abundance in small forest fragments.
Keywords: Cork oak; fragmentation; gall wasp; parasitism rate; parasitoid; Pyrenees; Quercus suber

Radial variation of wood density components and ring width in cork oak trees - Knapic, S; Louzada, J L; Leal, S; Pereira, H (Annals of forest science, 2007)
– The radial variation of ring width and wood density was studied in cork oaks (Quercus suber) using microdensitometry. The observations were made in young never debarked cork oaks (30–40 years of age) and in mature trees under cork production (37–60 years of age). The cork oak wood is very dense (mean ring density 0.86 g.cm−3 , between 0.79 g.cm−3 and 0.97 g.cm−3 ) with a small intra-ring variability (mean earlywood density 0.80 g.cm−3 and latewood density 0.90 g.cm−3 ). The density components decreased from pith to bark more rapidly until the 15th ring, and then only slightly. There were no signiﬁcant diﬀerences in the mean density components between never debarked trees and trees under cork production but their outwards decrease was accentuated in the never debarked trees. The annual growth was high, with a ring width mean of 3.9 mm (4.2 mm in the ﬁrst 30 years) and the latewood represented 57% of the annual growth.
Keywords: Cork oak; Density; latewood; Quercus suber; ring width

CERAMBICIDOS XILOFAGOS DEENCINAS Y ALCORNOQUES: ESTUDIO BIOECOLOGICO Y CONTROL DEPOBLACIONES - López Pantoja, G.; Sánchez-Osorio, I.; Domínguez, L. (Bol. Inf. CIDEU, 2006)
The aim of this work is to present recent advances on the knowledge of holm oak and cork oak woodborers (Coleoptera: Cerambycidae) in Huelva (Andalussia, Spain). Cerambyx welensii and Prinobius germari are considered the main implicated species. We emphasize over the differences of behavior founded among them: the first species is little territorial and very movable, Prinobius seems to show a more territorial and sedentary behavior, specially the males. After the analysis of diverse options for population control of insects with similar habits, a strategy of Integrated Management is recommended, having as one of his pillars the attraction of these species for his capture and/or the specific repelence or confusion; that is to say, the applied study of semiochemicals compounds to integrated pest management.
Keywords: Cerambyx; Cork oak; ehavior; Holm oak; Integrated Pest Management; Prinobius; woodborers

CERAMBICIDOS XILOFAGOS DEENCINAS Y ALCORNOQUES: ESTUDIO BIOECOLOGICO Y CONTROL DEPOBLACIONES - López Pantoja, G; Sánchez-Osorio, I; Domínguez, L (Bol. Inf. CIDEU, 2006)
The aim of this work is to present recent advances on the knowledge of holm oak and cork oak woodborers (Coleoptera: Cerambycidae) in Huelva (Andalussia, Spain). Cerambyx welensii and Prinobius germari are considered the main implicated species. We emphasize over the differences of behavior founded among them: the first species is little territorial and very movable, Prinobius seems to show a more territorial and sedentary behavior, specially the males. After the analysis of diverse options for population control of insects with similar habits, a strategy of Integrated Management is recommended, having as one of his pillars the attraction of these species for his capture and/or the specific repelence or confusion; that is to say, the applied study of semiochemicals compounds to integrated pest management.
Keywords: Cerambyx; Cork oak; ehavior; Holm oak; Integrated Pest Management; Prinobius; woodborers

Cork Oak Trees (Quercus suber L.). - Alvarez, Rubén; Toribio, Mariano; Cortizo, Millán; Ordás Fernández, Ricardo-Javier (Methods in molecular biology (Clifton, N.J.), 2006)
A transformation system for selected mature Quercus suber L. trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses are inoculated with AGL1 strain harbouring the plasmid pBINUbiGUSint, which carries the nptII and uidA genes. Evidence of stable transgene integration is obtained by polymerase chain reaction for nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos are germinated and successfully transferred to soil.
The following values have no corresponding Zotero field: periodical: Methods in molecular biology (Clifton, N.J.) accession-num: 17033056 electronic-resource-num: 10.1385/1-59745-131-2:113
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; kanamycin resistance; pBINUbiGUSint; Quercus suber; Somatic embryogenesis; Tree genetic transformation; β-glucuronidase

Cork Oak Trees (Quercus suber L.). - Alvarez, Rubén; Toribio, Mariano; Cortizo, Millán; Ordás Fernández, Ricardo-Javier (Methods in molecular biology (Clifton, N.J.), 2006)
A transformation system for selected mature Quercus suber L. trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses are inoculated with AGL1 strain harbouring the plasmid pBINUbiGUSint, which carries the nptII and uidA genes. Evidence of stable transgene integration is obtained by polymerase chain reaction for nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos are germinated and successfully transferred to soil.
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; kanamycin resistance; pBINUbiGUSint; Quercus suber; Somatic embryogenesis; Tree genetic transformation; β-glucuronidase

Morphological response and growth of cork oak (Quercus suber L.) seedlings at different shade levels - Cardillo, E; Bernal, C J (Forest Ecology and Management, 2006)
In spite of the importance of shade tolerance in silviculture, some species such as cork oak (Quercus suber L.) have not been well characterized. This work aims to describe the response of cork oak seedlings to a light gradient in their ﬁrst growing period. The seedlings were grown under different mesh ﬁlters and were watered to full ﬁeld capacity of the soil. The response to different light levels was studied in terms of morphology and growth, measuring heights, diameters, photosynthetic apparatus dimensions and shoot and root biomass. There were three plant extractions in April, June and October. The greatest morphological plasticity was noticed in the size of the leaves, which changed from 1.8 cm 2 under full sunlight to 5.8 cm 2 in maximum shade. The cork oak seedlings endured light levels of 20% at relative growth rates (RGR) similar to those under full sunlight. However, light intensities under 50% produced a smaller accumulation of root biomass. Plants under 5% of light showed clear symptoms of etiolation and their net assimilation rate was practically zero. These results will prove useful in silviculture, for instance, when determining the grade of protection in cork oak reforestations, as well as when deciding the system and period of regeneration and when regulating the liberation cuts of parent trees in stands of cork oak.
Keywords: Cork oak; growth analysis; Quercus suber; shading; tolerance

Morphological response and growth of cork oak (Quercus suber L.) seedlings at different shade levels - Cardillo, E.; Bernal, C. J. (Forest Ecology and Management, 2006)
In spite of the importance of shade tolerance in silviculture, some species such as cork oak (Quercus suber L.) have not been well characterized. This work aims to describe the response of cork oak seedlings to a light gradient in their ﬁrst growing period. The seedlings were grown under different mesh ﬁlters and were watered to full ﬁeld capacity of the soil. The response to different light levels was studied in terms of morphology and growth, measuring heights, diameters, photosynthetic apparatus dimensions and shoot and root biomass. There were three plant extractions in April, June and October. The greatest morphological plasticity was noticed in the size of the leaves, which changed from 1.8 cm 2 under full sunlight to 5.8 cm 2 in maximum shade. The cork oak seedlings endured light levels of 20% at relative growth rates (RGR) similar to those under full sunlight. However, light intensities under 50% produced a smaller accumulation of root biomass. Plants under 5% of light showed clear symptoms of etiolation and their net assimilation rate was practically zero. These results will prove useful in silviculture, for instance, when determining the grade of protection in cork oak reforestations, as well as when deciding the system and period of regeneration and when regulating the liberation cuts of parent trees in stands of cork oak.
Keywords: Cork oak; growth analysis; Quercus suber; shading; tolerance

Performance di recenti imboschimenti con quercia da sughero in ex-coltivi - Dettori, S; Falqui, A; Filigheddu, M R; Sedda, L (iForest - Biogeosciences and Forestry, 2006)
Recently, significant forestry activities have taken place in Sardinia thanks to EU Regulation 2080/92 funds. Some 80% of the afforestated surface has been planted with holm oak and cork oak. The latter also characterizes 89% of the reforestation area. Given the funding source, plantations have been established on farmlands. Growth performances of these recent cork oak stands have been quantitatively evaluated and compared with the performances of two experimental plots. In Gallura (north-east of Sardinia), that is the traditional cork production area and still is economically the most important cork district of the island, these new cork oak plantations have an average size of 28 ha. They have been established on lands that, before plantation, were either pastures (30%) or arable lands (70%). Plantation failures are limited to 8.8% of the total (in term of mass) and seem independent of environmental factors or plantations species composition (conifers have been frequently used as secondary species). Average growth of the stem, measured above cork at collar height, is in the range 4 to 8mm/year with a mean value of 5.5mm/year. No correlation appears with either environmental conditions or species composition of the plantations. In the first experimental plot, soil management practices (natural vegetation removal vs its cutting and mulching) does not differentiate young plants growth trends. In the control subplots (no removal) stem collar diameter is 20% smaller. Localized manual hoeing around trunk base increased the diameters by 13% but reduced cork thickness by 21%. The second experimental plot allows comparisons among 27 Mediterranean proveniences of cork oak. The trial exhibits reduced genetic influence: diameters and heights growth are significantly different only among extreme groups. In conclusion, reduced growth performances of the plantations established in farmlands is due, to some extent, to the limitations inherent with private land management (constrained to costs minimization) and, on the other hand, to the generally very limited thickness of Gallura soils. Demand for good quality commercial cork is steadily raising. To sustain the request, in the short term, it would be necessary to extend financial support for plantations care, from 5 to 10 years, or even up to the first stripping (virgin cork).
Keywords: Afforestation; Cork oak; Growth; Performance; Reg EEC 2080/92; Sardinia

Performance di recenti imboschimenti con quercia da sughero in ex-coltivi - Dettori, S.; Falqui, A.; Filigheddu, M. R.; Sedda, L. (iForest - Biogeosciences and Forestry, 2006)
Recently, significant forestry activities have taken place in Sardinia thanks to EU Regulation 2080/92 funds. Some 80% of the afforestated surface has been planted with holm oak and cork oak. The latter also characterizes 89% of the reforestation area. Given the funding source, plantations have been established on farmlands. Growth performances of these recent cork oak stands have been quantitatively evaluated and compared with the performances of two experimental plots. In Gallura (north-east of Sardinia), that is the traditional cork production area and still is economically the most important cork district of the island, these new cork oak plantations have an average size of 28 ha. They have been established on lands that, before plantation, were either pastures (30%) or arable lands (70%). Plantation failures are limited to 8.8% of the total (in term of mass) and seem independent of environmental factors or plantations species composition (conifers have been frequently used as secondary species). Average growth of the stem, measured above cork at collar height, is in the range 4 to 8mm/year with a mean value of 5.5mm/year. No correlation appears with either environmental conditions or species composition of the plantations. In the first experimental plot, soil management practices (natural vegetation removal vs its cutting and mulching) does not differentiate young plants growth trends. In the control subplots (no removal) stem collar diameter is 20% smaller. Localized manual hoeing around trunk base increased the diameters by 13% but reduced cork thickness by 21%. The second experimental plot allows comparisons among 27 Mediterranean proveniences of cork oak. The trial exhibits reduced genetic influence: diameters and heights growth are significantly different only among extreme groups. In conclusion, reduced growth performances of the plantations established in farmlands is due, to some extent, to the limitations inherent with private land management (constrained to costs minimization) and, on the other hand, to the generally very limited thickness of Gallura soils. Demand for good quality commercial cork is steadily raising. To sustain the request, in the short term, it would be necessary to extend financial support for plantations care, from 5 to 10 years, or even up to the first stripping (virgin cork).
The following values have no corresponding Zotero field: pub-location: Dipartimento di Economia e Sistemi arborei Universit di Sassari, via E. De Nicola 9, 07100 Sassari. publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Afforestation; Cork oak; Growth; Performance; Reg EEC 2080/92; Sardinia

Réponse des coléoptères saproxyliques à l’hétérogénéité des subéraies dans le massif des maures (France) - Brin, A. ; Brustel H. (Revue d'Ecologie la Terre et la Vie, 2006)
Saproxylic beetles’ response to cork-oak forests heterogeneity in the Massif des Maures (France). — Cork-oak stands are a major component of the “Massif des Maures” forests (France, Var). Depending on fi re frequency, soil conditions and human uses, these forests present different forms. Even if Mediterranean landscapes have been shaped for a long time by fi re, such recurrent perturbation may affect several functional groups of organisms associated with old forests, such as saproxylics insects. Our aims were (i) to investigate species richness and composition of saproxylic beetle assemblages in different cork-oak stands, (ii) to estimate between stand complementarity and (iii) identify indicator species of each habitat. Three different types of cork-oak stands common in the “Massif des Maures”, representing an increasing gradient of canopy closing and ecosystem maturing, were investigated : a senescent stand associated with mature maquis, an adult stand with high maquis and an open adult stand with low maquis. Beetles were sampled from April to August in 2003 and 2004 using baited window traps. Our results showed that : (i) the three studied cork-oak stands can be considered as three different habitats regarding saproxylic beetle assemblages, (ii) the closed cork-oak stands support the highest cumulative species richness, (iii) abundances of ecological groups show signifi cant between stands differences, (iv) each habitat supports remarkable species from a patrimonial point of view.
APSAPS
Keywords: Cork oak; France; saproxylic beetles

Réponse des coléoptères saproxyliques à l’hétérogénéité des subéraies dans le massif des maures (France) - Brin, A ; Brustel H (Revue d'Ecologie la Terre et la Vie, 2006)
Saproxylic beetles’ response to cork-oak forests heterogeneity in the Massif des Maures (France). — Cork-oak stands are a major component of the “Massif des Maures” forests (France, Var). Depending on fi re frequency, soil conditions and human uses, these forests present different forms. Even if Mediterranean landscapes have been shaped for a long time by fi re, such recurrent perturbation may affect several functional groups of organisms associated with old forests, such as saproxylics insects. Our aims were (i) to investigate species richness and composition of saproxylic beetle assemblages in different cork-oak stands, (ii) to estimate between stand complementarity and (iii) identify indicator species of each habitat. Three different types of cork-oak stands common in the “Massif des Maures”, representing an increasing gradient of canopy closing and ecosystem maturing, were investigated : a senescent stand associated with mature maquis, an adult stand with high maquis and an open adult stand with low maquis. Beetles were sampled from April to August in 2003 and 2004 using baited window traps. Our results showed that : (i) the three studied cork-oak stands can be considered as three different habitats regarding saproxylic beetle assemblages, (ii) the closed cork-oak stands support the highest cumulative species richness, (iii) abundances of ecological groups show signifi cant between stands differences, (iv) each habitat supports remarkable species from a patrimonial point of view.
APS
Keywords: Cork oak; France; saproxylic beetles

Within and between-tree variation in the biometry of wood rays and fibres in cork oak (Quercus suber_L.) - Leal, Sofia; Sousa, Vicelina B; Pereira, Helena (Wood Science and Technology, 2006)
The variability of ﬁbre and ray dimensions was studied at three radial positions (10, 50 and 90% of radius) in 5 cork oaks (Quercus suber L.) approximately 40 years old. Uniseriate ray height and cell number as well as multiseriate ray height and width were measured in tangential sections. Fibre length, width and wall thickness were measured after maceration. The most striking features of cork oak wood were the large multiseriate rays and the frequent homocellular uniseriate rays. On average multiseriate rays were 5.16 mm high and 0.48 mm wide, and uniseriate rays contained 11 cells and were 227 lm high. Neighbour rays presented large dimensional diﬀerences but there was no radial variation and there were very small between-tree diﬀerences. The radial maintenance of high and wide rays was discussed as a means to improve water shortage in response to water stress. Fibre dimensions increased radially but diﬀered little between trees: on average, 960–1,220 lm length, 18.40–21.49 lm width and 6.66–8.07 lm wall thickness. The ray pattern showed enough variation for visual appreciation while ensuring within and between-tree uniformity. The presence of rays has to be taken into consideration for designing wood drying programs.
Keywords: Cork oak; fibre biometry; wood anatomy; wood rays (PG)

Cytological analysis of early microspore divisions leading to gametic embryo formation in Quercus suber L. anther cultures - Pintos, B; Manzanera, J A; Bueno, M A (Acta Physiologiae Plantarum, 2005)
The cor re la tion be tween the phenologic stage of the in flo res - cence and the microspore de vel op ment stage was stud ied. Cyto log i cal ex am i na tions of the de vel op ment of micro spores dur - ing in vi tro an ther cul ture of cork oak (Quercus suber L.), were car ried out dur ing the first four weeks of cul ture. To ob serve the di vi sion oc cur ring in the micro spores, an thers were taken ran domly from the cultures after heat shock treatment and were stained with DAPI. Most of the an thers re spond ing to a heat stress treat ment con tained 91 % vacuolated micro spores, in di cat ing that this de vel op men tal stage is re spon sive to embryo genesis in duc tion in cork-oak micro spores. Af ter the heat shock treat ment some cork-oak micro spores were in duced and ini ti ated the embryogenic path way with the oc cur rence of nu mer ous sym met ric mi to sis, pro duc ing struc tures with two to ten or more nu clei. These lead to the for ma tion of high num - bers of multicellular cork-oak micro spores (pro-em bryos). Twenty-forty days af ter in duc tion, small white glob u lar and cotyledonal em bryos were ob served, which fur ther de vel oped root and shoot, re gen er at ing plantlets.
Keywords: anther culture; Cork oak; microspore embryogenesis; Quercus suber

Cytological analysis of early microspore divisions leading to gametic embryo formation in Quercus suber L. anther cultures - Pintos, B.; Manzanera, J. A.; Bueno, M. A. (Acta Physiologiae Plantarum, 2005)
The cor re la tion be tween the phenologic stage of the in flo res - cence and the microspore de vel op ment stage was stud ied. Cyto log i cal ex am i na tions of the de vel op ment of micro spores dur - ing in vi tro an ther cul ture of cork oak (Quercus suber L.), were car ried out dur ing the first four weeks of cul ture. To ob serve the di vi sion oc cur ring in the micro spores, an thers were taken ran domly from the cultures after heat shock treatment and were stained with DAPI. Most of the an thers re spond ing to a heat stress treat ment con tained 91 % vacuolated micro spores, in di cat ing that this de vel op men tal stage is re spon sive to embryo genesis in duc tion in cork-oak micro spores. Af ter the heat shock treat ment some cork-oak micro spores were in duced and ini ti ated the embryogenic path way with the oc cur rence of nu mer ous sym met ric mi to sis, pro duc ing struc tures with two to ten or more nu clei. These lead to the for ma tion of high num - bers of multicellular cork-oak micro spores (pro-em bryos). Twenty-forty days af ter in duc tion, small white glob u lar and cotyledonal em bryos were ob served, which fur ther de vel oped root and shoot, re gen er at ing plantlets.
Keywords: anther culture; Cork oak; microspore embryogenesis; Quercus suber

Designing decision support tools for Mediterranean forest ecosystems management: a case study in Portugal - Falcão, André O; Borges, José G (Ann. For. Sci., 2005)
The effectiveness of Mediterranean forest ecosystem management calls for the conceptualization and implementation of adequate decision support tools. The proposed decision support system encompasses a management information system, a prescription simulator, a constraint generator and a set of management models designed to solve decision problems. Emphasis is on the architecture of the prescription simulator and its linkage to the three other modules, as well as on methods for reporting and visualizing solutions. Results are discussed for a real world test case – Serra de Grândola, a management area with about 18 600 ha comprising 860 cork oak (Quercus suber L.) land units. Cork oak silviculture adds complexity to the traditional forest management problem. Results show that the devised system is able to address effectively the integration of ecosystem data, silviculture, growth-and-yield and management models. They further suggest that the proposed system architecture may help address the complexity of Mediterranean ecosystem management problems.
Keywords: Cork oak; decision support systems; Forest management; Mediterranean ecosystems; prescription simulation

Designing decision support tools for Mediterranean forest ecosystems management: a case study in Portugal - Falcão, André O.; Borges, Jose G. (Ann. For. Sci., 2005)
The effectiveness of Mediterranean forest ecosystem management calls for the conceptualization and implementation of adequate decision support tools. The proposed decision support system encompasses a management information system, a prescription simulator, a constraint generator and a set of management models designed to solve decision problems. Emphasis is on the architecture of the prescription simulator and its linkage to the three other modules, as well as on methods for reporting and visualizing solutions. Results are discussed for a real world test case – Serra de Grândola, a management area with about 18 600 ha comprising 860 cork oak (Quercus suber L.) land units. Cork oak silviculture adds complexity to the traditional forest management problem. Results show that the devised system is able to address effectively the integration of ecosystem data, silviculture, growth-and-yield and management models. They further suggest that the proposed system architecture may help address the complexity of Mediterranean ecosystem management problems.
Keywords: Cork oak; decision support systems; Forest management; Mediterranean ecosystems; prescription simulation

Effect of exogenous ABA on embryo maturation and quantification of endogenous levels of ABA and IAA in Quercus suber somatic embryos - Garcia-Martin, G. (Plant cell, tissue and …, 2005)
Knowledge of the relationship between indole-3-acetic acid (IAA) and abscisic acid (ABA) is relevant to control the development and the maturation of cork oak (Quercus suber L.) somatic embryos. The addition of 1 lM ABA to the culture medium signiﬁcantly promoted somatic embryo maturation and increased both fresh and dry matter without aﬀecting the relative water content. This eﬀect was parallel to the pattern of variation observed in the endogenous ABA level, which increased from the immature to the mature stage. Endogenous ABA content during the occurrence of secondary embryogenesis was similar to that of the immature stage, showing that embryos with lower ABA levels produced secondary embryos. In contrast, IAA showed the highest concentration during early embryo development and decreased afterwards. Only in somatic embryos subjected to 1-week desiccation followed by stratiﬁcation at 4 C for 2 weeks, was a moderate increment of endogenous IAA content observed. IAA and ABA showed opposite levels during the development and maturation of cork oak somatic embryos and characterised speciﬁc stages of the embryonic development.
Keywords: Cork oak; endogenous plant growth regulators; GC-MS; hplc; in vitro; somatic embryo

Effect of exogenous ABA on embryo maturation and quantification of endogenous levels of ABA and IAA in Quercus suber somatic embryos - GARCÍA-MARTÍN, G (Plant cell, tissue and …, 2005)
Knowledge of the relationship between indole-3-acetic acid (IAA) and abscisic acid (ABA) is relevant to control the development and the maturation of cork oak (Quercus suber L.) somatic embryos. The addition of 1 lM ABA to the culture medium signiﬁcantly promoted somatic embryo maturation and increased both fresh and dry matter without aﬀecting the relative water content. This eﬀect was parallel to the pattern of variation observed in the endogenous ABA level, which increased from the immature to the mature stage. Endogenous ABA content during the occurrence of secondary embryogenesis was similar to that of the immature stage, showing that embryos with lower ABA levels produced secondary embryos. In contrast, IAA showed the highest concentration during early embryo development and decreased afterwards. Only in somatic embryos subjected to 1-week desiccation followed by stratiﬁcation at 4 C for 2 weeks, was a moderate increment of endogenous IAA content observed. IAA and ABA showed opposite levels during the development and maturation of cork oak somatic embryos and characterised speciﬁc stages of the embryonic development.
Keywords: Cork oak; endogenous plant growth regulators; GC-MS; hplc; in vitro; somatic embryo

Effects of the interaction between drought and shade on water relations, gas exchange and morphological traits in cork oak (Quercus suber L.) seedlings - Aranda, I.; Castro, L.; Pardos, M.; Gil, L.; Pardos, J. a (Forest Ecology and Management, 2005)
The combined effect of drought and light on different physiological and biochemical traits was assessed in cork oak (Quercus suber L.) seedlings grown under two levels of light availability and submitted to a long-standing drought. Watering was withdrawn after germination and seedlings were allowed to dry to a water content of ca. 50% of ﬁeld capacity. At this point, water-stressed seedlings were grown under moderate drought and two light regimes: high light (HL—50%) and low light (LL— 2%). Soil water in control plants was kept close to ﬁeld capacity (90–100%) for both light environments. Water-relations parameters derived from P–V curves, gas exchange and water status at predawn (Cpd ) were evaluated at twice during the experiment. Nitrogen and chlorophyll contents were determined in the same leaves used for the gas exchange measurements. In addition, maximum rate of carboxylation (Vcmax) and electronic transport (Jmax) were derived from A–Ci curves in well-watered seedlings. The variation on moisture availability during the experiment was the same under both light environments. In control plants, Cpd was over 0.3 MPa at the two harvests, while stressed seedlings decreased to 0.9 MPa, with no differences between light treatments. Water stress decreased osmotic potentials at full (Cp100 ) and zero turgor (Cp0 ). The regressions between both potentials and Cpd showed a higher intercept in shade grown seedlings. This fact will point out the higher osmoregulation capacity in sun seedlings whatever water availability. Nitrogen investment on a per leaf mass (Nmass ), chlorophyll content (Chlmass ) and SLA tended to show a typical pattern of sun-shade acclimation. Thus, the three parameters increased with shade. Only for Nmass there was a signiﬁcant effect of watering, since water stress increased Nmass . LL plants showed a lower photosynthetic capacity in terms of maximum net photosynthesis at saturating light (Amax), which was related to a decrease in Vcmax and Jmax . Both parameters varied with speciﬁc leaf area (SLA) in a similar way. The low-light environment brought about a higher nitrogen investment in chlorophyll, while under high-light environment the investment was higher in carboxylation (Vcmax) and electronic transport ( Fmax). Stomatal conductance to water vapour (gwv ) and Amax were lower in low-light seedlings independently of watering. In addition, there was a trend to keep higher intrinsic water use efﬁciency (IWUE) under high light environment. The increase of IWUE under water stress was higher in HL seedlings. This was as consequence of the steeper decline in gwv as Cpd decreased. The decrease of Amax with Cpd occurred in a similar way in LL and HL seedlings. Thus, the HL seedlings tended to sustain a higher ability to increase IWUE than LL seedlings when they were submitted to the same water stress.
Keywords: Cork oak; Drought; light; osmotic adjustment; photosynthesis; water use efficiency

Microrganismos Associados à Cortiça em Diferentes Fases da sua Fileira - Santos, Maria Natércia; Bragança, Maria Helena; Casimiro, Pedro Piloto (Silva Lusitana, 2005)
Several microorganisms have been considered responsible for decrease in cork quality and wine off - flavours. To improve the knowledge on cork microbiology throughout the tree to end product (stopper) steps, the work developed included two components. The first, on fungal populations colonising the tree, aims to evaluate the probable role of the tree as source of both slab and stopper contamination. The second focusing the collection of dispersed information about the microbial populations, throughout the industrial cork steps, has a main objective to constitute a basis for the delineation of further studies on this matter. The integration of results allows the following conclusions: (i) the microbial populations change throughout cork manufacture process, reflecting both the different environmental conditions and methods used; (ii) the persistence of a large part of these populations throughout the several phases (tree to end product), indicates that the tree is, probably one of the most important microorganism source; (iii) a fraction of these populations included in the group are pointed out as capable of producing secondary metabolites that affect both cork and wine quality; (iv) no significant differences between microbial population diversity and tree vigour level were found. The results obtained did not allow a relationship between decrease of tree vigour and wine-off flavours. Dispersed and sometimes inaccurate information makes it difficult to build a consistent knowledge frame, indicating that a well - balanced multidiscipline research program including all the partners involved in cork processing, is an urgent necessity.
Keywords: associated microorganisms; Cork oak; cork stopper manufacture

Microrganismos Associados à Cortiça em Diferentes Fases da sua Fileira - Santos, Maria Natércia; Bragança, Maria Helena; Casimiro, Pedro Piloto (Silva Lusitana, 2005)
Several microorganisms have been considered responsible for decrease in cork quality and wine off - flavours. To improve the knowledge on cork microbiology throughout the tree to end product (stopper) steps, the work developed included two components. The first, on fungal populations colonising the tree, aims to evaluate the probable role of the tree as source of both slab and stopper contamination. The second focusing the collection of dispersed information about the microbial populations, throughout the industrial cork steps, has a main objective to constitute a basis for the delineation of further studies on this matter. The integration of results allows the following conclusions: (i) the microbial populations change throughout cork manufacture process, reflecting both the different environmental conditions and methods used; (ii) the persistence of a large part of these populations throughout the several phases (tree to end product), indicates that the tree is, probably one of the most important microorganism source; (iii) a fraction of these populations included in the group are pointed out as capable of producing secondary metabolites that affect both cork and wine quality; (iv) no significant differences between microbial population diversity and tree vigour level were found. The results obtained did not allow a relationship between decrease of tree vigour and wine-off flavours. Dispersed and sometimes inaccurate information makes it difficult to build a consistent knowledge frame, indicating that a well - balanced multidiscipline research program including all the partners involved in cork processing, is an urgent necessity.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: associated microorganisms; Cork oak; cork stopper manufacture

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber - Díaz-Fernández, Pedro M.; Climent, José; Gil, Luis (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed
Keywords: Cork oak; iberian peninsula; Phenology; quiescent flowers; ripening cycle

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber - Díaz-Fernández, Pedro M; Climent, José; Gil, Luis (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed
Keywords: Cork oak; iberian peninsula; Phenology; quiescent flowers; ripening cycle

Genetic transformation of selected mature cork oak (Quercus suber L.) trees. - Álvarez, R; Alonso, P; Cortizo, M; CELESTINO, C; HERNÁNDEZ, I; TORIBIO, M; Ordás, R J (Plant cell reports, 2004)
A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens strain AGL1. Evidence of stable transgene integration was obtained by PCR for the nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos were germinated and successfully transferred to soil.
Keywords: Agrobacterium; Cork oak; Fagaceae; Somatic embryogenesis; Tree genetic transformation

Genetic transformation of selected mature cork oak (Quercus suber L.) trees. - Alvarez, R.; Alonso, P.; Cortizo, M.; Celestino, C.; Hernández, I.; Toribio, M.; Ordás, R. J. (Plant cell reports, 2004)
A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens strain AGL1. Evidence of stable transgene integration was obtained by PCR for the nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos were germinated and successfully transferred to soil.
The following values have no corresponding Zotero field: accession-num: 15185122
Keywords: Agrobacterium; Cork oak; Fagaceae; Somatic embryogenesis; Tree genetic transformation

Identification of Portuguese Armillaria Isolates by Classic Mating-Tests and RFLP-PCR Analysis of the ITS1 Region of Ribosomal DNA - Bragança, Helena; Tenreiro, Rogério; Santos, Natércia (Silva Lusitana, 2004)
The diagnosis of Armillaria, a genus including distinct species of highly woody plantpathogenic root-infecting fungi with worldwide distribution, is usually based on morphological characteristics and mating-tests, although the PCR-based restriction fragment length polymorphism (RFLP-PCR), specifically in nuclear rDNA spacers, have also been applied. In the present study, mating-tests and restriction analysis of Internal Transcribed Spacer 1 (ITS1) were used to identify 20 isolates of a Portuguese Armillaria collection. Although the majority of the diploid isolates (80%) could be identified in diploid-haploid pairings, the method is laborious, takes too much time (up to 2 months), and presents a high rate of inconclusive results. The ITS1 region showed to be a reliable molecular marker for A. mellea, in particular when HinfI restriction analysis is applied, since two fragments with 245 bp and 125 bp have been obtained for this most aggressive species whereas 290 bp and 70 bp were produced from isolates of the other European species. As simple molecular techniques are involved and the whole procedure can be performed in one day, A. mellea identification by ITS1 analysis is a clearly accessible and more advantageous tool to plant pathology laboratories, mainly those involved on the control and preservation of forest trees
Keywords: Armillaria mellea; Cork oak; rDNA; RFLP-PCR; Woody plants

Identification of Portuguese Armillaria Isolates by Classic Mating-Tests and RFLP-PCR Analysis of the ITS1 Region of Ribosomal DNA - Bragança, Helena; Tenreiro, Rogério; Santos, Natércia (Silva Lusitana, 2004)
The diagnosis of Armillaria, a genus including distinct species of highly woody plantpathogenic root-infecting fungi with worldwide distribution, is usually based on morphological characteristics and mating-tests, although the PCR-based restriction fragment length polymorphism (RFLP-PCR), specifically in nuclear rDNA spacers, have also been applied. In the present study, mating-tests and restriction analysis of Internal Transcribed Spacer 1 (ITS1) were used to identify 20 isolates of a Portuguese Armillaria collection. Although the majority of the diploid isolates (80%) could be identified in diploid-haploid pairings, the method is laborious, takes too much time (up to 2 months), and presents a high rate of inconclusive results. The ITS1 region showed to be a reliable molecular marker for A. mellea, in particular when HinfI restriction analysis is applied, since two fragments with 245 bp and 125 bp have been obtained for this most aggressive species whereas 290 bp and 70 bp were produced from isolates of the other European species. As simple molecular techniques are involved and the whole procedure can be performed in one day, A. mellea identification by ITS1 analysis is a clearly accessible and more advantageous tool to plant pathology laboratories, mainly those involved on the control and preservation of forest trees
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: Armillaria mellea; Cork oak; rDNA; RFLP-PCR; Woody plants

Micropropagation du Chêne-liège (Quercus suber L.) par culture d'apex issus d'axes embryonnaires - El Kbiach, Mohamed L'bachir; Lamarti, Ahmed; Abdali, Abdeslam; Badoc, Alain (Acta Botanica Gallica, 2004)
Abstract To improve the in vitro germination and development of cork oak embryonic axes, several mineral media were tested; Durzan medium modified 1/2 supplemented with 400 mg/l glutamine and 3% sucrose gave the best results. The action of BA alone or combined with other growth regulators was also studied. A low concentration (0.44 ?M) was found to give an acceptable percentage of plantlets. When combined with NAA, callogenesis was observed. The transfer of cultures in conditions of low luminosity led to the formation of several axillary buds. These buds were multiplied on a solid medium supplemented with GA3 at low concentration. The buds were elongated, then rooted on a growth regulator-free medium after brief dipping in an auxinic solution. The rooted plants were potted on horticultural substrate.
doi: 10.1080/12538078.2004.10515443
Keywords: Cork oak; embryonic axis; in vitro culture; organogenesis; Quercus suber

Micropropagation du Chêne-liège (Quercus suber L.) par culture d'apex issus d'axes embryonnaires - El Kbiach, Mohamed L'bachir; Lamarti, Ahmed; Abdali, Abdeslam; Badoc, Alain (Acta Botanica Gallica, 2004)
Abstract To improve the in vitro germination and development of cork oak embryonic axes, several mineral media were tested; Durzan medium modified 1/2 supplemented with 400 mg/l glutamine and 3% sucrose gave the best results. The action of BA alone or combined with other growth regulators was also studied. A low concentration (0.44 ?M) was found to give an acceptable percentage of plantlets. When combined with NAA, callogenesis was observed. The transfer of cultures in conditions of low luminosity led to the formation of several axillary buds. These buds were multiplied on a solid medium supplemented with GA3 at low concentration. The buds were elongated, then rooted on a growth regulator-free medium after brief dipping in an auxinic solution. The rooted plants were potted on horticultural substrate.
doi: 10.1080/12538078.2004.10515443doi: 10.1080/12538078.2004.10515443The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Cork oak; embryonic axis; in vitro culture; organogenesis; Quercus suber

Micropropagation of cork oak (Quercus suber L.) by apical bud culture from embryonic axes - El Kbiach, M L; Lamarti, A; Abdali, A; Badoc, A (ACTA BOTANICA GALLICA, 2004)
To improve the in vitro germination and development of cork Oak embryonic axes, several mineral media were tested; Durzan medium modified 1/2 supplemented with 400 mg/l glutamine and 3% sucrose gave the best results. The action of BA alone or combined with other growth regulators was also studied. A low concentration (0.44 mu M) was found to give an acceptable percentage of plantlets. When combined with NAA, callogenesis was observed. The transfer of cultures in conditions of low luminosity led to the formation of several axillary buds. These buds were multiplied on a solid medium supplemented with GA(3) at low concentration. The buds were elongated, then rooted on a growth regulator-free medium after brief dipping in an auxinic solution. The rooted plants were potted on horticultural substrate.
Keywords: Cork oak; embryon; in vitro culture; Quercus suber

Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M. L.; Lamarti, A.; Abdali, A.; Badoc, A. (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M L; Lamarti, A; Abdali, A; Badoc, A (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

Vegetative propagation of Quercus suber L. by somatic embryogenesis. I. Factors affecting the induction in leaves from mature cork oak trees. - HERNÁNDEZ, I; CELESTINO, C; TORIBIO, M (Plant cell reports, 2003)
Somatic embryogenesis was induced in expanding leaves from epicormic shoots forced to sprout from segments of branches collected from several hundred-year-old cork oak trees. Following a basic protocol previously defined for leaves taken from seedlings of this species, several factors were studied to improve the response. The induction frequency was significantly higher when the length of exposure to growth regulators was increased from 7 to 30 days. The combined application of NAA and BAP was essential for induction. Although both regulators had a very significant influence, their interaction was not significant, suggesting independent roles. Leaf size had a crucial effect, because beyond a certain threshold, embryogenesis could not be obtained. Embryogenic lines were maintained via repetitive embryogenesis on hormone-free medium for more than 2 years.
Keywords: Clonal propagation; Cork oak; Quercus suber; Somatic embryogenesis

Vegetative propagation of Quercus suber L. by somatic embryogenesis. II. Plant regeneration from selected cork oak trees. - HERNÁNDEZ, I; CELESTINO, C; ALEGRE, J; TORIBIO, M (Plant cell reports, 2003)
The regeneration of somatic seedlings from selected 100-year-old cork oak trees is reported. The induction of somatic embryogenesis from leaves of epicormic shoots was significantly affected by genotype, harvesting time and their interaction. Leaves from all five selected trees produced somatic embryos when the segments of branches used as sources of epicormic shoots were collected in May. Genotype, but not the level of photosynthetically active radiation, affected the proliferation of the embryogenic lines and the number of detachable embryos that could be obtained from them. Genotype also affected several steps leading to conversion of somatic embryos, from germination to complete acclimatisation of somatic seedlings. Almost 40% of the somatic embryos from all lines germinated, showing coordinated root and shoot growth. Although the mean percentage of recovery for the whole process was low, plants could be regenerated from four of the five trees tested.
Keywords: Clonal propagation; Cork oak; Quercus suber; Selected trees; Somatic embryogenesis

Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle - Costa, Augusta; Pereira, Helena; Oliveira, Ângelo (Ann. For. Sci., 2002)
The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1. The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compared to wood. Tree radial growth presented a clear within-the-year seasonal pattern, extending from March to October, with a maximum in June-July. The overall pattern of monthly growth distribution was similar among the years of the production cycle, but some inter-annual variations occurred with 1-2 month shifts or monthly growth rate decreases, related to climatic factors. Early spring growth was enhanced by winter rain, autumn growth by high summer rain and June increments by high temperatures during this month.
Keywords: climatic fluctuations; cork growth; Cork oak; dendroclimatology; diameter growth

Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle - Costa, Augusta; Pereira, Helena; Oliveira, Ângelo (Ann. For. Sci., 2002)
The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1. The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compared to wood. Tree radial growth presented a clear within-the-year seasonal pattern, extending from March to October, with a maximum in June-July. The overall pattern of monthly growth distribution was similar among the years of the production cycle, but some inter-annual variations occurred with 1-2 month shifts or monthly growth rate decreases, related to climatic factors. Early spring growth was enhanced by winter rain, autumn growth by high summer rain and June increments by high temperatures during this month.
Keywords: climatic fluctuations; cork growth; Cork oak; dendroclimatology; diameter growth

Shoot development in Quercus suber L. somatic embryos - Gonzalez-Benito, M Elena; García-Martín, Gemma; Antonio Manzanera, José (In Vitro Cellular & Developmental Biology - Plant, 2002)
N 6 -Benzyladenine (BA; 0.04–4 mM) application to germinated Quercus suber somatic embryos considerably increased caulinar apex elongation frequency and maintained active growth in the plantlets, although it did not have a signiﬁcant effect on the percentage of shoots with normal morphology. The addition of 0.5 mM indoleacetic acid together with the cytokinin did not have any effect. The use of a low concentration (0.04mM) of BA allowed the appropriate radicle elongation in all germinating somatic embryos, but higher concentrations arrested this elongation.
Keywords: Cork oak; growth regulators; in vitro; plantlet.

A spatial statistical analysis of cork oak competition in two Portuguese silvopastoral systems - Paulo, M. J.; Stein, A.; Tomé, M. (Canadian Journal of Forest Research, 2002)
This paper considers competition among cork oaks (Quercus suber L.) at three plots in two representative Portuguese stands. It uses spatial point pattern functions to describe densities and quantify differences among stands. Relations between cork oak characteristics and indices measuring intertree competition are modelled. Tree competition has a significant effect on tree crown characteristics. In particular, cork oaks with much competition have smaller and more elongated crowns. A standard model that relates crown diameter with diameter at breast height was improved. The R2 value increased from 0.53 to 0.63 by including a crown shape parameter and competition indices.
doi: 10.1139/x02-107doi: 10.1139/x02-107The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: Competition (voyant); Cork oak; crown characteristics

Catkin frost damage in Mediterranean cork-oak (Quercus suber L.). - García-mozo, Herminia; Hidalgo, Pablo J; Galán, Carmen; Gómez-Casero, Maria Teresa; Domínguez, Eugenio (Israel Journal of Plant Sciences, 2001)
During a period of study of floral phenology and pollen production in the cork-oak, Quercus suber L. (199799), an interruption of catkin development was detected in spring 1998. The cause might have been a sharp drop in minimum temperatures during that period, which coincided with the initial stages of microsporogenesis. Results show that environmental temperatures close to 0 ºC halted microsporogenesis and catkinelongation, resulting in their complete death. No fruits were observed in the affected zone, as a possible consequence of the lack of pollen. Phenological, histological, andaerobiological data are analyzed as a whole in order to gain a better understanding of the phenomenon. Cold spells during flowering may be one of the factors influencing the high interannual variability of acorn production in Quercus species. [ABSTRACT FROM AUTHOR]
Keywords: CATKIN-bearing plants; Cork oak; flowers; Fruit; Phenology; PLANT spores; POLLEN (citation)

Catkin frost damage in Mediterranean cork-oak (Quercus suber L.). - García-mozo, Herminia; Hidalgo, Pablo J.; Galán, Carmen; Gómez-Casero, Maria Teresa; Domínguez, Eugenio (Israel Journal of Plant Sciences, 2001)
During a period of study of floral phenology and pollen production in the cork-oak, Quercus suber L. (199799), an interruption of catkin development was detected in spring 1998. The cause might have been a sharp drop in minimum temperatures during that period, which coincided with the initial stages of microsporogenesis. Results show that environmental temperatures close to 0 ºC halted microsporogenesis and catkinelongation, resulting in their complete death. No fruits were observed in the affected zone, as a possible consequence of the lack of pollen. Phenological, histological, andaerobiological data are analyzed as a whole in order to gain a better understanding of the phenomenon. Cold spells during flowering may be one of the factors influencing the high interannual variability of acorn production in Quercus species. [ABSTRACT FROM AUTHOR]
Keywords: CATKIN-bearing plants; Cork oak; flowers; Fruit; Phenology; PLANT spores; POLLEN (citation)

EARLY CHECKING OF GENETIC STABILITY OF CORK OAK SOMATIC EMBRYOS BY AFLP ANALYSIS. - Hornero, J.; Martinez, I.; Celestino, C.; Gallego, F. J.; Torres, V.; Toribio, M. (International Journal of Plant Sciences, 2001)
Early checking of the genetic stability, of tissue culture-derived plants is necessary to obtain all the potential benefits of clonal forestry. Previous work in Quercus suber L. using random amplified polymorphic DNA (RAPD) markers showed no genetic variation among somatic embryos within embryogenic lines of zygotic origin. Genetic fingerprinting based on amplified fragment length polymorphisms (AFLP) allows the direct analysis of variation at the entire DNA level by generating more reproducible markers than RAPDs. To confirm the absence of genetic variation within six embryogenic lines of zygotic origin, six primer pairs were selected out of 48 combinations of primers for revealing up to 512 AFLP markers, 301 of them (58.8%) being polymorphic. The mean number of markers per genotype was 375. Again differences were recorded among embryogenic lines, even between those that arose from half-sib zygotic embryos, but no variation was observed among somatic embryos within embryogenic lines. To check variation in embryogenic lines raised from non-embryonic tissues, somatic embryogenesis was induced in expanding leaves collected from sprouts originating in three mature cork oak. DNA was extracted from leaves and from somatic embryos derived from each tree, and three primer pairs showed 165, 110, and 108 markers per genotype/tree, respectively. In one tree, AFLP patterns generated from leaves and somatic embryos were identical, but variation was detected in samples from the other two trees. Although the level of genetic variation detected in these lines (5.6% and 7.3% of polymorphism, respectively) is lower than that recorded for half sibs of cork oak (25%–31%), its influence on phenotypic variation needs further assessment. [ABSTRACT FROM AUTHOR]
Keywords: AFLP; Cork oak; DNA markers; in vitro culture; Quercus suber; somaclonal variation; Somatic embryogenesis

EARLY CHECKING OF GENETIC STABILITY OF CORK OAK SOMATIC EMBRYOS BY AFLP ANALYSIS. - Hornero, J; Martinez, I; CELESTINO, C; Gallego, F J; Torres, V; TORIBIO, M (International Journal of Plant Sciences, 2001)
Early checking of the genetic stability, of tissue culture-derived plants is necessary to obtain all the potential benefits of clonal forestry. Previous work in Quercus suber L. using random amplified polymorphic DNA (RAPD) markers showed no genetic variation among somatic embryos within embryogenic lines of zygotic origin. Genetic fingerprinting based on amplified fragment length polymorphisms (AFLP) allows the direct analysis of variation at the entire DNA level by generating more reproducible markers than RAPDs. To confirm the absence of genetic variation within six embryogenic lines of zygotic origin, six primer pairs were selected out of 48 combinations of primers for revealing up to 512 AFLP markers, 301 of them (58.8%) being polymorphic. The mean number of markers per genotype was 375. Again differences were recorded among embryogenic lines, even between those that arose from half-sib zygotic embryos, but no variation was observed among somatic embryos within embryogenic lines. To check variation in embryogenic lines raised from non-embryonic tissues, somatic embryogenesis was induced in expanding leaves collected from sprouts originating in three mature cork oak. DNA was extracted from leaves and from somatic embryos derived from each tree, and three primer pairs showed 165, 110, and 108 markers per genotype/tree, respectively. In one tree, AFLP patterns generated from leaves and somatic embryos were identical, but variation was detected in samples from the other two trees. Although the level of genetic variation detected in these lines (5.6% and 7.3% of polymorphism, respectively) is lower than that recorded for half sibs of cork oak (25%–31%), its influence on phenotypic variation needs further assessment. [ABSTRACT FROM AUTHOR]
Keywords: AFLP; Cork oak; DNA markers; in vitro culture; Quercus suber; somaclonal variation; Somatic embryogenesis

Estudio de la influencia de la fertilizacion nitrogenada y la iluminacion sobre atributos morfologicos y fisiologicos de brinzales de Q.suber L. CULTIVADO EN VIVERO. RESULTADOS DEL 1er. AÑO EN CAMPO - Martínez Romero, G.; Planelles González, R.; Zazo Muncharaz, J.; Bela Quero, D.; Vivar Sanz, A.; López Arias, M. (III Congreso Forestal Español Congreso, 2001)
This essay studies the influence of fertilization and illumination of Q.suber L. in container seedlings. Plants were tested in three diferents levels of fertilization (control substrate, fertilizated substrate and fertilizated substrate plus nitrogen supplied) with two of illumination (full light conditions and a reduction of 50% illumination). After the first year in nursery, plants was installed in survey parcels, where growing measures and survival rates were studied
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso pub-location: Granada
Keywords: Cork oak; fertilization; ilumination; Quercus suber L.

Estudio de la influencia de la fertilizacion nitrogenada y la iluminacion sobre atributos morfologicos y fisiologicos de brinzales de Q.suber L. CULTIVADO EN VIVERO. RESULTADOS DEL 1er. AÑO EN CAMPO - Martínez Romero, G; Planelles González, R; Zazo Muncharaz, J; Bela Quero, D; Vivar Sanz, A; López Arias, M (III Congreso Forestal Español Congreso, 2001)
This essay studies the influence of fertilization and illumination of Q.suber L. in container seedlings. Plants were tested in three diferents levels of fertilization (control substrate, fertilizated substrate and fertilizated substrate plus nitrogen supplied) with two of illumination (full light conditions and a reduction of 50% illumination). After the first year in nursery, plants was installed in survey parcels, where growing measures and survival rates were studied
Keywords: Cork oak; fertilization; ilumination; Quercus suber L.

Relaciones hídricas en procedencias de QUERCUS SUBER L. - Castro, L.; Aranda, I.; Gil, L.; Pardos, J. A. (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso
Keywords: Cork oak; osmotic adjustment; pressure-volume curves; water potential

Relaciones hídricas en procedencias de QUERCUS SUBER L. - Castro, L; Aranda, I; Gil, L; Pardos, J A (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.
Keywords: Cork oak; osmotic adjustment; pressure-volume curves; water potential

Testing the conservation of Quercus spp. microsatellites in the cork oak, Q-suber L. - Hornero, J; Gallego, F J; Martinez, I; TORIBIO, M (SILVAE GENETICA, 2001)
The transferability of microsatellite (SSR) loci from Quercus spp. to cork oak (Quercus suber L.) was investigated. Semi-automated analysis of fluorescently-labelled PCR fragments was used to test 24 primer sets developed for Q. myrsinifolia BLUME, Q. petraea (MAT7.) LIEB. and Q. robur L. in 41 cork oak trees from four stands covering the main area of distribution of the species in Spain. Successful cross-species events occurred for 13 loci (54%). Two of them were monomorphic and another two appeared as multilocus. High levels of genetic variability were detected both for the number of alleles, 62 (7.5 per polymorphic locus, with a maximum number of 19 in locus ssrQpZAG110) and for the expected heterozygosity (mean H-E = 0.648). These results were much higher than those previously reported by other authors using allozyme loci. The usefulness of the. SSR loci successfully amplified for studies on population genetics of cork oak is discussed.
Keywords: Cork oak; Fagaceae; microsatellites; Quercus suber

Haploid origin of cork oak anther embryos detected by enzyme and RAPD gene markers. - Bueno, M. A.; Agundez, M. D. (International Journal of Plant Sciences, 2000)
Examines the haploid origin of cork oak anther embryos using enzyme and RAPD gene marker analysis. Exploration of the gene coding of shikimate dehydrogenase; Factor influencing the non-identification of another genotypes by isozyme analysis; Implication of detected banding patterns for the existence of multiple microspore origins.
Keywords: Cork oak; Haploid; Quercus suber; RAPD markers

Haploid origin of cork oak anther embryos detected by enzyme and RAPD gene markers. - Bueno, M A; Agundez, M D (International Journal of Plant Sciences, 2000)
Examines the haploid origin of cork oak anther embryos using enzyme and RAPD gene marker analysis. Exploration of the gene coding of shikimate dehydrogenase; Factor influencing the non-identification of another genotypes by isozyme analysis; Implication of detected banding patterns for the existence of multiple microspore origins.
Keywords: Cork oak; Haploid; Quercus suber; RAPD markers

Mycorrhization of vitroplants raised from somatic embryos of cork oak (Quercus suber L.) - Dı́ez, Jesús; Manjón, José Luis; Kovács, Gabor M; Celestino, Cristina; Toribio, Mariano (Applied Soil Ecology, 2000)
The technique described herein allows in vitro ectomycorrhizal synthesis in Quercus suber vitroplants raised from somatic embryos with Pisolithus tinctorius and Scleroderma polyrhizum strains. Only strains of this species coming from fruit bodies collected in Quercus suber stands (strain QS241 and strain QS247) formed ectomycorrhizas, and hence these species seem to exhibit host adaptation. The in vitro mycorrhization facilitated the development of secondary roots and the ex vitro weaning of cork oak vitroplants.
Keywords: Cork oak; ectomycorrhizas; Mycorrhization; Somatic embryogenesis

Mycorrhization of vitroplants raised from somatic embryos of cork oak (Quercus suber L.) - Dı́ez, Jesús; Manjón, José Luis; Kovács, Gabor M.; Celestino, Cristina; Toribio, Mariano (Applied Soil Ecology, 2000)
The technique described herein allows in vitro ectomycorrhizal synthesis in Quercus suber vitroplants raised from somatic embryos with Pisolithus tinctorius and Scleroderma polyrhizum strains. Only strains of this species coming from fruit bodies collected in Quercus suber stands (strain QS241 and strain QS247) formed ectomycorrhizas, and hence these species seem to exhibit host adaptation. The in vitro mycorrhization facilitated the development of secondary roots and the ex vitro weaning of cork oak vitroplants.
Keywords: Cork oak; ectomycorrhizas; Mycorrhization; Somatic embryogenesis

Past distribution and ecology of the cork oak (Quercus suber) in the Iberian Peninsula: a pollen-analytical approach - Carrión, J S; Parra, I; Navarro, C; Munuera, M (Diversity and Distributions, 2000)
This study presents pollen-analytical data from continental and offshore Iberian Peninsula sites that include pollen curves of Quercus suber, to provide information on the past distribution and ecology of the cork oak (Q. suber). Results centre on a new pollen record of Navarrés (Valencia, eastern Spain), which shows that the cork oak survived regionally during the Upper Pleistocene and was important during a mid-Holocene replacement of a local pine forest by Quercus-dominated communities. This phenomenon appears linked to the recurrence of ﬁre and reinforces the value of the cork oak for reforestation programmes in ﬁre-prone areas. In addition to Navarrés, other Late Quaternary pollen sequences (Sobrestany, CasablancaAlmenara, Padul, SU 8103, SU8113, 8057B) suggest last glacial survival of the cork oak in southern and coastal areas of the Peninsula and North Africa. Important developments also occur from the Late Glacial to the middle Holocene, not only in the west but also in the eastern Peninsula. It is suggested that, in the absence of human inﬂuence, Q. suber would develop in non-monospeciﬁc forests, sharing the arboreal stratum both with other sclerophyllous and deciduous Quercus and Pinus species
Keywords: Cork oak; historical biogeography; iberian peninsula; palaeoecology; pollen.

Past distribution and ecology of the cork oak (Quercus suber) in the Iberian Peninsula: a pollen-analytical approach - Carrión, J. S.; Parra, I.; Navarro, C.; Munuera, M. (Diversity and Distributions, 2000)
This study presents pollen-analytical data from continental and offshore Iberian Peninsula sites that include pollen curves of Quercus suber, to provide information on the past distribution and ecology of the cork oak (Q. suber). Results centre on a new pollen record of Navarrés (Valencia, eastern Spain), which shows that the cork oak survived regionally during the Upper Pleistocene and was important during a mid-Holocene replacement of a local pine forest by Quercus-dominated communities. This phenomenon appears linked to the recurrence of ﬁre and reinforces the value of the cork oak for reforestation programmes in ﬁre-prone areas. In addition to Navarrés, other Late Quaternary pollen sequences (Sobrestany, CasablancaAlmenara, Padul, SU 8103, SU8113, 8057B) suggest last glacial survival of the cork oak in southern and coastal areas of the Peninsula and North Africa. Important developments also occur from the Late Glacial to the middle Holocene, not only in the west but also in the eastern Peninsula. It is suggested that, in the absence of human inﬂuence, Q. suber would develop in non-monospeciﬁc forests, sharing the arboreal stratum both with other sclerophyllous and deciduous Quercus and Pinus species
Keywords: Cork oak; historical biogeography; iberian peninsula; palaeoecology; pollen.

Biodiversity of woody species in oak woodlands of southern Spain and northern Morocco - MARAÑÓN, T; Ajbilou, R; Ojeda, F; Arroyo, J (Forest Ecology and Management, 1999)
Three biodiversity parameters ± species richness, endemic species richness and taxonomic singularity ± have been evaluated for the woody understorey of oak woodlands on sandstone-derived substrates, on both sides of the Strait of Gibraltar. There is a similarity in ¯oristic composition and ecological distribution of woody plant communities across the Strait. Nevertheless, we have detected signi®cant differences. These include a general reduction in species richness, number of endemic species and taxonomic singularity (at the community level), and a greater abundance of widespread, generalist species, on the southern side (Moroccan) communities, as compared to the north (Spanish ones). We interpret these differences as partly caused by the contrasting management of woodlands, with higher slashing and browsing pressure in Morocco.
Keywords: Cork oak; diversity; Mediterranean woodlands; Quercus; Species richness; strait of gibraltar

INFORMACIÓN ACERCA DE LA PRESENCIA DE ALCORNOQUE ( Quercus suber L .) EN LA PROVINCIA DE GUADALAJARA - SERRADA HIERRO, R; García Viñas, J I (Investigación agraria. Sistemas y recursos forestales, 1999)
The paper gathers information on the so believed only natural presence of cork oak (Quercus suber L.) in the province of Guadalajara (Central Spain). It is the extremest eastern location of that species in the southern face of the Central Range of Mountains. The most important botanical, ecological and dasometrical aspects of the stand are described. An ecological homologation of the stand, based on Allué Andrade’s work, has also been carried out.
Keywords: Cork oak; Guadalajara; Quercus suber

Post forest-fire hydrochemical behaviour of the Rimbaud catchment (Massif des Maures, France) - Martin, C; Chevalier, Y (ZEITSCHRIFT FUR GEOMORPHOLOGIE, 1999)
In August 1990, a forest fire devastated 84 % of the Rimbaud catchment area (1.46 km(2)). This catchment presents a substratum composed of gneiss. Its relief is sharp. Soils are skeletal. The forest fire destroyed a maquis (with treelike heather and arbustus) interspersed with cork oaks and maritime pines. The fire's effects on the chemical composition of the runoff have remained light in terms of low flows. On the other hand, mineralization has greatly increased during flood, especially at the beginning of the 1990-91 water year. The paper reports on the observations conducted during four years after the fire. Dissolved outputs and hydrochemical balances are compared with results obtained on the same catchment before the forest fire, and on the Boussicaut catchment (0.74 km(2)), which is very close by, but which was not burnt.
APS
Keywords: chemical composition; Cork oak; forest fire; Maquis; maritime pine; runoff

Sexual reproduction in the cork oak (Quercus suber L.). I. The progamic phase - Boavida, L C; Varela, M C; Feijo, J A (Sexual Plant Reproduction, 1999)
Cork oak (Quercus suber L.) is a monoecious wind-pollinated species with a protandrous system to ensure cross-pollination. To the best of our knowledge, this report provides the first insight into the sexual reproduction cycle in this species. The cork oak flowering season extends from April until the end of May. Our results show that, at anthesis, the pistillate flower is not completely formed and ovules are just starting to develop. Pollen reaching the dry stigmatic surface adheres to the receptive cells, germinates and penetrates the epidermis in aproximately 24 h, and grows through the intercellular spaces of a solid transmitting tissue. In cross-pollination, a sequential arrest of pollen tubes was observed along the style, providing preliminary evidence for a pollen tube competition mechanism. As a consequence, few pollen tubes reach the basal portion of the style. Furthermore, pollen tube growth is a discontinuous process since tubes are arrested in the basal portion of the style about 10–12 days after pollination. While tubes are latent, the ovarian loculus starts to develop from an emerging mass of sporogeneous cells which later will differentiate into the placenta and ovules. One and a half months after pollination ovules complete their differentiation, tubes resume growth and fertilisation occurs. Ovular abortion is frequent at this stage, and only one ovule will successfully mature during autumn into a monospermic seed.
Keywords: Cork oak; Ovule abortion; Pollen tube arrest; Pollen tube competition; Quercus suber

Sexual reproduction in the cork oak (Quercus suber L.). I. The progamic phase - Boavida, L. C.; VARELA, M. C.; Feijo, J. A. (Sexual Plant Reproduction, 1999)
Cork oak (Quercus suber L.) is a monoecious wind-pollinated species with a protandrous system to ensure cross-pollination. To the best of our knowledge, this report provides the first insight into the sexual reproduction cycle in this species. The cork oak flowering season extends from April until the end of May. Our results show that, at anthesis, the pistillate flower is not completely formed and ovules are just starting to develop. Pollen reaching the dry stigmatic surface adheres to the receptive cells, germinates and penetrates the epidermis in aproximately 24 h, and grows through the intercellular spaces of a solid transmitting tissue. In cross-pollination, a sequential arrest of pollen tubes was observed along the style, providing preliminary evidence for a pollen tube competition mechanism. As a consequence, few pollen tubes reach the basal portion of the style. Furthermore, pollen tube growth is a discontinuous process since tubes are arrested in the basal portion of the style about 10–12 days after pollination. While tubes are latent, the ovarian loculus starts to develop from an emerging mass of sporogeneous cells which later will differentiate into the placenta and ovules. One and a half months after pollination ovules complete their differentiation, tubes resume growth and fertilisation occurs. Ovular abortion is frequent at this stage, and only one ovule will successfully mature during autumn into a monospermic seed.
Keywords: Cork oak; Ovule abortion; Pollen tube arrest; Pollen tube competition; Quercus suber

Ecology and history of a wooded landscape in southern Spain - MARAÑÓN, T; Ojeda, J F (ECOLOGICAL HISTORY OF EUROPEAN FORESTS, 1998)
An extensive oak woodland, of about 1000 km(2), dominated by evergreen cork oak (Quercus suber) and semideciduous Q. canariensis, is found in southern Spain, near the Strait of Gibraltar, and contrasts with the paradigm of deforested Mediterranean mountains. Several factors, ecological, geographical and historical, have contributed to the origin and maintenance of this forested landscape. The rough relief and the acidic, nutrient-poor soils (derived from Oligo-Miocene sandstone) made this area unsuitable for cultivation. The oceanic influence favours the growth of oak trees. In particular, the cork oak is well suited to acidic soils and the humid Mediterranean climate. Three historical milestones seem relevant to the preservation of this woodland. Its location at a frontier during medieval times (thirteenth to fifteenth centuries) discouraged villages and reduced human pressure on the woodland resources. The rise of the value of cork helped to preserve the cork oak woodland during early nineteenth. century industrial times. contemporary consciousness about the conservation of woodland landscapes (somewhat unusual in the Mediterranean region) led to their designation as Los Alcornocales (meaning `The cork oak woodlands') Natural Park, devoted to the eco-development of the region.
Keywords: Cork oak; forest landscape; human pressure; Mediterranean climate; Oak woodlands; Quercus canariensis; Quercus suber

The use of cork oak in the ecological and landscape restoration of the Latium Hills - Bellarosa, R; Schirone, B; Busatto, M (SYMPOSIUM ON PLANT BIOTECHNOLOGY AS A TOOL FOR THE EXPLOITATION OF MOUNTAIN LANDS, 1998)
The cork oak (Quercus suber L.) is a western Mediterranean species frequently found in Italy along the Tyrrhenian coast and on the islands. Its economic importance is well known, but the species is also ecologically precious. Notably, in fact, it is extremely resistant to forest fires. Because of its properties a project is on its way to restore the marginal lands of northern Latium through the reforestation with selected specimens of cork oak. The main aims of the project are: the genetic comparison between cork oak of different Italian provenances the establishment of an experimental arboretum which will collect cork oak deriving from the 34 main European areas the running of experimental trials on innovative reforestation techniques, such as the Miyawaki method. The methodology and initial results of the project are reported.
Keywords: arboretum; Cork oak; Genetic variability; reforest

EFECTO DE DISTINTOS TIPOS DE ENVASE, SUSTRATO y GRADOS DE ENDURECIMIENTO EN LA PRODUCCIÓN DE PLANTA DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM. - SUÁREZ, Ma ANGELES; ÁZQUEZ, FRANCISCO V; Baselga, Pilar (II Congreso Forestal Español, 1997)
Different treatments about olm oak (Quercus rotundifolia Lam.) and cork oak (Quercus suber L.) plants' production are comparied. It has been worked with two kinds of containers, three kinds of substratums and two degrees of plants' protection during the cultivation
Keywords: Cork oak; Nursery; Olm oak; Plant's production; Quercus

EFECTOS DE DISTINTOS TRATAMIENTOS EN VIVERO EN EL ARRAIGO Y PRIMER DESARROLLO EN CAMPO DE PLANTAS DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM .. EFECTO DEL PROTECTOR. - Suarez, M Ángeles; VÁzquez, Francisco; Baselga, Pilar; Torres, Enrique; CUEVAS, SERAFÍN (II Congreso Forestal Español, 1997)
The rootting ability and the first developes of cork oak and olm oak seedlings cultivated on different substratums and containers, as well as different harding degrees are comparied. The individual protector's effect is also analyzed.
Keywords: Cork oak; Nursery; Olm oak; Plant's production; Quercus; Reforestation

Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A; GÓMEZ, A; Boscaiu, M; Manzanera, J A; Vicente, O (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; Haploid plants; Stress

Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A.; GÓMEZ, A.; Boscaiu, M.; Manzanera, J. A.; Vicente, O. (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: anther culture; Cork oak; Haploid plants; Stress

Liquid medium culture of Quercus suber L somatic embryos comparation between liquid and solid culture and among different growing media - Garcia, G.; Fernandez-Galiano, E.; Mauri, P. V. (HORTICULTURAL BIOTECHNOLOGY IN VITRO CULTURE AND BREEDING, 1997)
The objective of this study was to overcome two of the limiting factors of the standard culture protocol, in agar solidified medium, of cork oak somatic embryos: the low rate of mature embryos obtained, and the high labor and time consumed. First experiment. Immature somatic embryos of 2 mm. length were cultured for 30 days in four different growing media: 1/2SH{*}, SH{*}, 2xSH{*} and MS, both in solid and liquid phase. Higher fresh weights were detected, in every media, using liquid culture. In relation to developmental pattern, liquid culture in 1/2SH{*} has demonstrated to be the most effective combination for the first developmental stages producing lower percentages of secondary embryogenesis. Second experiment. Immature somatic embryos were cultured for 15 days in liquid 1/2SH{*} and transferred to the four different media. The richest media were shown to be more appropriated for the maturation stage giving higher rates of mature embryos.
The following values have no corresponding Zotero field: periodical: HORTICULTURAL BIOTECHNOLOGY IN VITRO CULTURE AND BREEDING issue: 447 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: Cork oak; liquid culture; mature embryos

Liquid medium culture of Quercus suber L somatic embryos comparation between liquid and solid culture and among different growing media - Garcia, G; Fernandez-Galiano, E; Mauri, P V (HORTICULTURAL BIOTECHNOLOGY IN VITRO CULTURE AND BREEDING, 1997)
The objective of this study was to overcome two of the limiting factors of the standard culture protocol, in agar solidified medium, of cork oak somatic embryos: the low rate of mature embryos obtained, and the high labor and time consumed. First experiment. Immature somatic embryos of 2 mm. length were cultured for 30 days in four different growing media: 1/2SH{*}, SH{*}, 2xSH{*} and MS, both in solid and liquid phase. Higher fresh weights were detected, in every media, using liquid culture. In relation to developmental pattern, liquid culture in 1/2SH{*} has demonstrated to be the most effective combination for the first developmental stages producing lower percentages of secondary embryogenesis. Second experiment. Immature somatic embryos were cultured for 15 days in liquid 1/2SH{*} and transferred to the four different media. The richest media were shown to be more appropriated for the maturation stage giving higher rates of mature embryos.
Keywords: Cork oak; liquid culture; mature embryos

Multiplicación vegetativa de alcornoque mediante embriogénesis somática. - GARCÍA-MARTÍN, G; Fernandez-Galiano, E; Mauri, P V; Somática, Embriogénesis (II Congreso Forestal Español, 1997)
In order to obtain cork oak clones from selected individuals, somatic embryogenesis was induced in leaves. Somatic embryos can be continuously subcultured with high proliferation rates. This culture system has sorne limiting factors: low percentage of mature embryos obtained, low rate of shoot emergence during germination and high labour and time consumed. Exogenous addition of ABA (l0-6M) concentration during proliferation increased maturation rateo In the same way addition of. BAP (0,001 mg/l) had a positive effect on shoot production. With the aim to obtain a first approach to automation the best culture media for both culture cycles of maturation in liquid medium were determined.
Keywords: ABA; BaP; Cork oak; germination; liquid culture; maturation; somatic embryos

Multiplicación vegetativa de alcornoque mediante embriogénesis somática. - Garcia-Martin, G.; Fernandez-Galiano, E.; Mauri, P. V.; Somática, Embriogénesis (II Congreso Forestal Español, 1997)
In order to obtain cork oak clones from selected individuals, somatic embryogenesis was induced in leaves. Somatic embryos can be continuously subcultured with high proliferation rates. This culture system has sorne limiting factors: low percentage of mature embryos obtained, low rate of shoot emergence during germination and high labour and time consumed. Exogenous addition of ABA (l0-6M) concentration during proliferation increased maturation rateo In the same way addition of. BAP (0,001 mg/l) had a positive effect on shoot production. With the aim to obtain a first approach to automation the best culture media for both culture cycles of maturation in liquid medium were determined.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: ABA; BaP; Cork oak; germination; liquid culture; maturation; somatic embryos

Resprouting of Quercus suber in NE Spain after fire - Pausas, J G (Journal of Vegetation Science, 1997)
Many Mediterranean species have evolved strategies that allow them to survive periodic wildfires. Quercus suber trees resprout after fire, some from stem buds and others from basal buds only. In the former case the canopy recovers quickly. In the latter case the stem dies but the tree survives and regrows from basal sprouts. The probability of stem death and the degree of height recovery were studied after a fire in a Q. suber forest in NE Spain using logistic regression analysis. The results suggest that most trees survive after fire; the probability of stem death is negatively related to tree diameter; and recovery is positively related to tree diameter and to bark thickness. Implication for management and conservation of cork-oak forests are discussed.
Keywords: Cork oak; disturbance; Mediterranean; sprouting

Seed Proteins from Quercus suber - Fonseca, Paula A; Ferreira, Ricardo B; Teixeira, Artur R (Journal of Agricultural and Food Chemistry, 1997)
A study on the extraction and characterization of the cotyledonary proteins from cork oak (Quercus suber L.) seeds is reported. The seed proteins, which constitute approximately 5% of the seed weight, are glutelins on the basis of solubility criteria. They are readily solubilized in sodium borate buffer, pH 10, 50 mM, containing 1% (v/v) ?-mercaptoethanol and 1% (w/v) sodium dodecyl sulfate. This fraction is made up of a large number of polypeptides with molecular masses ranging from 10 to above 100 kDa and occurs in the form of large aggregates. The level of glycosylation is low, with two main glycopolypeptides present (43 and 65 kDa). However, the major polypeptides are not glycosylated. In vitro digestibility studies indicated that trypsin and α-chymotrypsin produce a partial proteolysis of the cotyledonary proteins, particularly among the larger molecular mass polypeptides. The partial proteolysis seen in trypsin digests is not due to the presence of enzyme inhibitors in the seeds. On the other hand, pepsin almost completely digests the seed proteins. Taken together, these results may be considered as a good indication of the potential nutritional quality of the proteins from Q. suber seeds. Keywords: Cork oak; glutelin; in vitro proteolysis; protein; Quercus suber; seed
doi: 10.1021/jf9609486
Keywords: Cork oak; glutelin; in vitro proteolysis; protein; Quercus suber; seed

Seed Proteins from Quercus suber - Fonseca, Paula A.; Ferreira, Ricardo B.; Teixeira, Artur R. (Journal of Agricultural and Food Chemistry, 1997)
A study on the extraction and characterization of the cotyledonary proteins from cork oak (Quercus suber L.) seeds is reported. The seed proteins, which constitute approximately 5% of the seed weight, are glutelins on the basis of solubility criteria. They are readily solubilized in sodium borate buffer, pH 10, 50 mM, containing 1% (v/v) ?-mercaptoethanol and 1% (w/v) sodium dodecyl sulfate. This fraction is made up of a large number of polypeptides with molecular masses ranging from 10 to above 100 kDa and occurs in the form of large aggregates. The level of glycosylation is low, with two main glycopolypeptides present (43 and 65 kDa). However, the major polypeptides are not glycosylated. In vitro digestibility studies indicated that trypsin and α-chymotrypsin produce a partial proteolysis of the cotyledonary proteins, particularly among the larger molecular mass polypeptides. The partial proteolysis seen in trypsin digests is not due to the presence of enzyme inhibitors in the seeds. On the other hand, pepsin almost completely digests the seed proteins. Taken together, these results may be considered as a good indication of the potential nutritional quality of the proteins from Q. suber seeds. Keywords: Cork oak; glutelin; in vitro proteolysis; protein; Quercus suber; seed
doi: 10.1021/jf9609486doi: 10.1021/jf9609486The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork oak; glutelin; in vitro proteolysis; protein; Quercus suber; seed

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress

Testing somaclonal variation using RAPDs in Quercus suber L. somatic embryos. - Gallego, F. J.; Martinez, I. (International Journal of Plant Sciences, 1997)
Focuses on the use of Random Amplified Polymorphic Deoxyribose nucleic acid (RAPD) profiles to test somaclonal variation in Quercus suber L. somatic embryous during recurrent embryogenesis. Number of primers used to amplify DNA from isolated embryos; Use of somatic embryogenesis from immature zygotic embryos; How somaclonal variation was detected.
Keywords: Cork oak; SOMATIC embryogenesis (citation)

Testing somaclonal variation using RAPDs in Quercus suber L. somatic embryos. - Gallego, F J; Martinez, I (International Journal of Plant Sciences, 1997)
Focuses on the use of Random Amplified Polymorphic Deoxyribose nucleic acid (RAPD) profiles to test somaclonal variation in Quercus suber L. somatic embryous during recurrent embryogenesis. Number of primers used to amplify DNA from isolated embryos; Use of somatic embryogenesis from immature zygotic embryos; How somaclonal variation was detected.
Keywords: Cork oak; SOMATIC embryogenesis (citation)

Assessment of mineral nutrition of cork oak through foliar analysis - Robert, Bénédicte; Bertoni, Georges; Sayag, Daniel; Masson, Philippe (Communications in Soil Science and Plant Analysis, 1996)
Abstract The changes in the mineral nutrient content of the leaves of an evergreen species, the cork oak (Quercus suber L.), were investigated to assess the possibilities of a diagnosis of the mineral nutrition of this forest species. A comprehensive pattern of change in the leaf contents of N, P, and Ca was then put forward from the data obtained. Among the time intervals that are most favorable to analyses, the end of the vegetative rest period, in January, was investigated more precisely. The variation coefficients of the leaf contents measured tree by tree were determined for a number of nutrients (N, P, K, Ca, Mg, Fe, Cu, Zn, Mn, B, Al, and Cl). The foliar analyses carried out on 7? to 10?month old leaves in stands submitted to various forest management practices led to the characterization of significant differences in P, Ca and Mn leaf contents in relation to the treatments applied.
Keywords: Cork oak; leaf content; Mineral nutrition; Quercus suber

Origin and early development of secondary embryos in Quercus suber L. - Puigderrajols, P; Fernández-Guijarro, B (International Journal of Plant Sciences, 1996)
Investigates the origin and early developmental patterns of secondary embryos of the cork oak Quercus suber L. Experimental procedure; Signs of secondary embryo formation; Color of proliferation of masses; Cellular isolation.
Keywords: Cork oak; EMBRYOS

Bases para um programa de melhoramento florestal da espécie Quercus suber L. - Ribeiro, M M A (Revista Florestal, 1995)
The existing symptoms of degradation in cork oak stands requires the improvement on them, namely with plants that might produce cork in quantity and of good quality. It is urgent to develop an improvement program for this species spread in 664 thousand ha in our country (i. e. 1/3 of the whole area covered with cork oak in the world). Fifty five per cent of the world cork production comes from that area whose size could be extended more than 200 thousand ha. In the present work improvement programs for forestry species are brought into focus, and so are the different techniques of vegetative propagation, due to the importance they have in the development of these programs related either to the mass phenotypic selection (to estimate heritability and genetic gain) or to the clonal propagation of improved material. Maturative process in forest trees is questioned once it might condition the use of vegetative propagation and the techniques used to overcome that process are referred. Finally strategies for the improvement of cork oak, in the short and long term, are named.
Keywords: Cork oak; forest tree improvement; Quercus suber L.; vegetative propagation

Influence of external factors on secondary embryogenesis and germination in somatic embryos from leaves of Quercus suber - Fernández-Guijarro, Bárbara; Celestino, Cristina; Toribio, Mariano (Plant Cell, Tissue and Organ Culture, 1995)
Somatic embryogenesis was obtained in cultures of leaves from young seedlings of Quercus suber L. A two- stage process, in which benzyladenine and naphthaleneacetic acid were added first at high and then at low concentrations, was required to initiate the process. Somatic embryos arose when the explants were subsequently placed on medium lacking plant growth regulators. The embryogenic lines remained productive, by means of secondary embryogenesis, on medium without growth regulators. However, this repetitive induction was influenced by the macronutrient composition of the culture medium. Both low total nitrogen content and high reduced nitrogen concentration decreased the percentage of somatic embryos that showed secondary embryogenesis. Our results suggest that alternate culture on medium that increases embryo proliferation and a low salt medium prohibiting embryo formation will partially synchronize embryo development. Chilling slightly reduced secondary embryogenesis but gave a modest increase in germination. Maturation under light followed by storage at 4 °C for at least 30 days gave the best results in switching embryos from an embryogenic pathway to a germinative one. Under these conditions 15% of embryos showed coordinated root and shoot growth and 35% formed either shoots or mostly roots. These percentages were higher than those of embryos matured in darkness. This result indicates that a specific treatment is required after maturation and before chilling to activate the switch from secondary embryo formation to germination.
Keywords: Cork oak; culture media; plant regeneration; recurrent embryogenesis; repetitive embryogenesis; Somatic embryogenesis

Influence of external factors on secondary embryogenesis and germination in somatic embryos from leaves of Quercus suber - Fernández-Guijarro, Bárbara; Celestino, Cristina; Toribio, Mariano (Plant Cell, Tissue and Organ Culture, 1995)
Somatic embryogenesis was obtained in cultures of leaves from young seedlings of Quercus suber L. A two- stage process, in which benzyladenine and naphthaleneacetic acid were added first at high and then at low concentrations, was required to initiate the process. Somatic embryos arose when the explants were subsequently placed on medium lacking plant growth regulators. The embryogenic lines remained productive, by means of secondary embryogenesis, on medium without growth regulators. However, this repetitive induction was influenced by the macronutrient composition of the culture medium. Both low total nitrogen content and high reduced nitrogen concentration decreased the percentage of somatic embryos that showed secondary embryogenesis. Our results suggest that alternate culture on medium that increases embryo proliferation and a low salt medium prohibiting embryo formation will partially synchronize embryo development. Chilling slightly reduced secondary embryogenesis but gave a modest increase in germination. Maturation under light followed by storage at 4 °C for at least 30 days gave the best results in switching embryos from an embryogenic pathway to a germinative one. Under these conditions 15% of embryos showed coordinated root and shoot growth and 35% formed either shoots or mostly roots. These percentages were higher than those of embryos matured in darkness. This result indicates that a specific treatment is required after maturation and before chilling to activate the switch from secondary embryo formation to germination.
Keywords: Cork oak; culture media; plant regeneration; recurrent embryogenesis; repetitive embryogenesis; Somatic embryogenesis

MULTIPURPOSE GENE CONSERVATION IN QUERCUS-SUBER - A PORTUGUESE EXAMPLE - Varela, M C; ERIKSSON, G (SILVAE GENETICA, 1995)
Quereus suber, the native forest tree of highest economic value to Portugal is continuously declining. Creating good conditions for future evolution is the most important gene conservation objective for Quercus suber A simple breeding programme to improve the production of good cork is also included in the gene conservation objective. Gene conservation of species accompanying Quercus suber, or even dependent on Quercus suber, is a third objective. The suggested sampling of gene resource populations is mainly based on climatic, soil and management conditions of Quercus suber populations. Active selection of trees with good cork in small multiple populations growing over a broad array of site conditions is suggested to match the joint evolutionary and breeding objective in gene conservation. Management of large natural populations to create maximum habitat diversity is suggested to take care of the gene conservation of accompanying species. Knowledge of the genetic structure of Quercus suber and of gene now is urgently needed and ought to be given priority in genetic research.
Author
Keywords: Cork oak; GENE CONSERVATION OBJECTIVES AND METHODS; Quercus suber; RESEARCH NEEDS

MULTIPURPOSE GENE CONSERVATION IN QUERCUS-SUBER - A PORTUGUESE EXAMPLE - VARELA, M. C.; ERIKSSON, G. (SILVAE GENETICA, 1995)
Quereus suber, the native forest tree of highest economic value to Portugal is continuously declining. Creating good conditions for future evolution is the most important gene conservation objective for Quercus suber A simple breeding programme to improve the production of good cork is also included in the gene conservation objective. Gene conservation of species accompanying Quercus suber, or even dependent on Quercus suber, is a third objective. The suggested sampling of gene resource populations is mainly based on climatic, soil and management conditions of Quercus suber populations. Active selection of trees with good cork in small multiple populations growing over a broad array of site conditions is suggested to match the joint evolutionary and breeding objective in gene conservation. Management of large natural populations to create maximum habitat diversity is suggested to take care of the gene conservation of accompanying species. Knowledge of the genetic structure of Quercus suber and of gene now is urgently needed and ought to be given priority in genetic research.
AuthorAuthorThe following values have no corresponding Zotero field: pub-location: FINKENHOFSTRASSE 21, D-60322 FRANKFURT, GERMANY publisher: J D SAUERLANDERS VERLAG
Keywords: Cork oak; GENE CONSERVATION OBJECTIVES AND METHODS; Quercus suber; RESEARCH NEEDS

Predators of Lymantria dispar (Lep. Lymantriidae) egg masses: Spatio-temporal variation of their impact during the 1988-89-pest generation in the Mamora cork oak forest (Morocco). - Villemant, C; Ramzi, H (ENTOMOPHAGA, 1995)
In the Mamora cork oak forest (Morocco), oophagous predators of the gypsy moth Lymantria dispar (L.) (Lepidoptera: Lymantriidae) are one of the main mortality factors influencing pest population dynamics. The predators destroy egg masses more by disrupting their cohesiveness than by predation. From 1987 to 1990, the impact of oophagous enemies significantly contributed to the collapse of a localized gypsy moth outbreak. Variation of egg mass dislocation intensity was greater between trees than among the different strata of a tree. The number of gypsy moth egg masses and egg predator attacks increased when oaks were large and unhealthy. Forest degradation probably explains why egg mass destruction rates were so high (60 to 90% of the eggs) in the infested forest. Oophagous predators find food and shelter under the dehiscent bark of unhealthy cork oaks.
Keywords: Cork oak; egg predator; Gypsy moth; Population Dynamics; spatial distribution

Propagação do sobreiro (Quercus suber) por estacaria - Ribeiro, Maria Margarida Chagas de Ataíde (1994)
Realizaram-se ensaios de enraizamento com estacas provenientes de jovens sobreiros, durante dois anos consecutivos. A aplicação de AIB à base da estaca melhorou a percentagem de enraizamento e a sobrevivência em relação à testemunha, na época de enraizamento de Abril. Na época de fins de Junho, já não se verificou a referida resposta positiva. Este tratamento não teve efeito no número de raízes formadas, por estaca enraizada, mas influenciou o comprimento da maior raiz, também por estaca enraizada, independentemente da época de enraizamento. A utilização de 0,1% ANA não provocou resultados diferentes da testemunha para qualquer dos parâmetros avaliados. O descasque na base da estaca aumentou a percentagem de enraizamento e a sobrevivência. Este tratamento, juntamente com a aplicação de 0,5% de AIB conduziu a percentagens de enraizamento superiores a 60%, ao fim de três meses de ensaio, na época de enraizamento de Abril. Quer a origem da estaca (topo ou base da planta) quer os tratamentos dos pés-mãe (colocação das plantas às escuras ou o escurecimento - uso de uma fita preta na base da futura estaca) não influenciaram a percentagem de enraizamento. A sobrevivência das estacas é comprometida na época de enraizamento de fins de Junho, pelo facto de entrarem em dormência. A aplicação de BAP às estacas enraizadas, em dormência, estimulou o abrolhamento de gomos axilares e não se observaram efeitos fitotóxicos. Realizaram-se cortes histológicos na base de estacas sujeitas ao tratamento de escurecimento (com ou sem aplicação de AIB na banda preta). No dia 0 observaram-se diferenças na estrutura devidas a esse tratamento especialmente ao nível da periderme e do xilema. Até ao dia 20 as diferenças estruturais das estacas submetidas ao tratamento de escurecimento foram-se acentuando com perda de coerência e aparecimento, por vezes abundante, de callus. Em geral as modificações surgiam na zona do nó e só depois na zona do entrenó. A aplicação de AIB à base da estaca antes de esta ser posta a enraizar não conduziu a diferenças tão evidentes como o tratamento de escurecimento
Keywords: Anatomy; Cork oak; Cuttings; Quercus suber L.; rooting; vegetative propagation

Ensayo de enraizamiento de estaquillas del alcornoque (Quercus suber L.) - Ribeiro, M M A (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
An experiment was made in order to study the tooting process in cuttings of young cork oaks. Different treatments with indol butiric acid (IBA) in different concentrations, two different origins of the cutting (basal and apical) and two different base of the cutting treatements (with or without bark removal) were performed. The best performances were achieved with 0.5% and 1 % of IBA (not significatively different) with 54 and 52 % of rooting, respectivly, after 3 months. The first treatment not only produces more roots by cutting but longer ones as well. Bark removal has the same effect but it does not improve rooting. The origin of the cutting had no influence in the studied parameters.
Keywords: Cork oak; Cuttings; Quercus suber L.; rooting; vegetative propagation

OBTENCION DE PLANTAS A PARTIR DE EMBRIONES SOMATICOS DE QUERCUS SUBER L - Fernández Guijarro, B.; Celestino, C.; Toribio, M. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This paper gives a procedure to regenerate plants of cork oak through somatic embryogenesis. The somatic embryos were obtained in leaves from young seedlings and cotyledonary fragments from mature acorns of cork oak. The explants were cultured in three stage process in wich BA and NAA concentration were decreasing. Different methods were used to germinate the embryos. Dessication and culture in low salt concentration medium were chosen to give the best results
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: adventive embryogenesis; Cork oak; culture media; plant regeneration; secondary embryogenesis

OBTENCION DE PLANTAS A PARTIR DE EMBRIONES SOMATICOS DE QUERCUS SUBER L - Fernández Guijarro, B; CELESTINO, C; TORIBIO, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This paper gives a procedure to regenerate plants of cork oak through somatic embryogenesis. The somatic embryos were obtained in leaves from young seedlings and cotyledonary fragments from mature acorns of cork oak. The explants were cultured in three stage process in wich BA and NAA concentration were decreasing. Different methods were used to germinate the embryos. Dessication and culture in low salt concentration medium were chosen to give the best results
Keywords: adventive embryogenesis; Cork oak; culture media; plant regeneration; secondary embryogenesis

Anatomía y caracterización del sistema radicular del alcornoque - VERDAGUER, D; Molinas, M L (SCIENTIA gerundensis, 1992)
In this paper we describe the root system of a mature cork oak (Quercus suber L). The roots were excavated by hand methods, seccioned and weighed. Large sections were described anatomically and sections smaller than 10 mm of diameter by histological tecniques. The root system components were distributed into central root system (CRS) and peripheral root system (PRS). The CRS was located at the base of the tree and embraced an area of 1'5 m and a depth of 60 cm; it consisted of the root crown, thick horizontal or descending roots and thin roots. The PRS extended in a circle of 12 m in diameier. In the PRS, the thick roots were distributed more laxly and the thin roots predominated. At their basal portion, the descending roots were eccentric and eliptic and rapidly forked into two or more small- diameter branches. Grafting between root axes was frequent. The horizontal roots were perpendicular to the tree axis, they were quite circular and kept thickness more or less constant since they forked. Large-diameter root tips, white coloured were observed and their primary structure described. Neither on the root crown nor at the base of the roots, lateral huds were observed.
Keywords: Cork oak; Quercus suber L.; root; root anatomy; root system

CONSIDERAçõES SOBRE OS RESULTADOS JA OBTIDOS NA PROPAGACAO VEGETATIVA DO SOBREIRO. ESTACARIA E ENXERTIA - Roldão, I F; Alpuim, M H; Bohm, J (Scientia gerundensis, 1992)
This work documents the first results of cork oak vegetative propagation by cuttings in a controlled envuonment. The followings traits are analyzed : substrates, hormones, au and substrate temperature andrelative bumidity etc.. Results from bud graftings in the multiplication of plus trees are also referenced
Keywords: Cork oak; Cuttings; grafting; Quercus Suber L; vegetative propagation

ENTOMOLOGICAL ASPECTS OF THE PROTECTION OF QUERCUS-SUBER L FORESTS IN SARDINIA - PROTA, R; DELRIO, G; FLORIS, I; LENTINI, A; LUCIANO, P (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
In the Sardinian cork oak forests, more than 300 species of Lepidoptera have been found, 10% of which develop on Quercus suber L. trees. The population density of these insects varies greatly, and, in some cases, is so high that causes total defoliation on large scale. Three species in particular cause serious damage: Lymantria dispar L., and Malacosoma neustria L. with periodic infestations and Tortrix viridana L. with temporary ones. There are also other, less harmful species, such as Dryobota labecula Esp., Dryobotodes monochroma Esp., Dryobotodes eremita Fabr., Orthosia cruda Den. & Schiff., Spudaea ruticilla Esp. and Phalera bucephala (L.) that have different fluctuations which can be described as latent or periodic (3).
Keywords: Cork oak; defoliation; lepidoptera; Sardinia

Impacte do Platypus cylindrus F.(Coleoptera, Platypodidae) en Quercus suber L - Ferreira, M. C.; Ferreira, G. W. S. (Scientia gerundensis, 1992)
The main symptoms of attacked trees by Platypus cylindrus F. are given. Data on bioecology, dispersion and impact of this species on Quercus suber L. are presented. Protection mesures.
Keywords: Cork oak; Platypus cylindrus F.; Quercus Suber L

Las técnicas de selección y propagación en la mejora genética del alcornoque - García Valdecantos, J. L. (Scientia gerundensis, 1992)
The role and importance of the techniques of propagation and selection in the cork oak breeding programs are discussed. In the field of propagation, the characteristics of sexuai reproduction are discussed. The author recommends the use of medium or small acorns and empbasizes the need of improving acorn storage procedures. Considering vegetative propagation as the best method to obtain maximal genetic gains, the author emphasizes the difficulties found in the use of cuttings, the fairly good results obtained with grafts, and the promising experiences of tissue culture. The importance of rejuvenating techniques using stump sprouts and suckers for vegetative propagation is strongly emphasized. The selection superior trees for breeding programs in the cork oak is difficult because of the lack of previous experience in genetics of bark production. An experimental method, developed in the province of Cidiz with the help of ICONA, is described. This method is based in an accurate measurement of a number of tree pararneters which are evaluated at the end of a complete harvest cycle (9 years).
Keywords: Cork oak; provenances; seed orchards; tree breeding; vegetative propagation

Plant regeneration through somatic embryogenesis in Quercus suber - Bueno, M. A.; Astorga, R.; Manzanera, J. A. (Physiologia Plantarum, 1992)
Cork oak (Quercus suber L.) zygotic embryos, endosperm and ovules were treated with different concentrations of 2,4-D for induction of somatic embryos. Plant material was collected during the embryo development season, from June to September. Immature embryos proved to be the most reactive initial explant. Callus and somatic embryos developed a few weeks after the beginning of the 2,4-D treatment. For embryo development experiments, different growth regulators and cold and desiccation treatments were tested. Cold storage of somatic embryos matured in vitro at 5°C was the best treatment for breaking dormancy.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cork oak; plant regeneration; Quercus suber; Somatic embryogenesis; tissue culture

POTENCIALIDAD DEL TERRITORI0 PARA EL ALCORNOQUE EN EXTREMADURA - GONZÁLEZ ADRADOS, J R; Elena Rosselló, R; Tella Ferreiro, G (Scientia gerundensis, 1992)
Most important aspects of a work titled 4ork oak Atlas of Extremaduran are presented here. A set of maps about: cork oak stands distribution; cork quality in the several zones; and ecological factors wich may limit the appearence of cork oak stands, are elaborated from the availahle thematic cartography. The Geographical Information SystemPC-ARC-IhFO ha beenused to get it. The final result is the Land Suitability for Cork Oak and Cork Quality Map of Extremadura. This map defines for the whole studied area the relative cork quaiity to be obteined and the presence of ecological factors wich may be adverse or exclusive for cork oak.
Keywords: Cork oak; Cork quality; land classification; Quercus suber; thematic cartography

POTENCIALIDAD DEL TERRITORI0 PARA EL ALCORNOQUE EN EXTREMADURA - González Adrados, J. R.; Elena Rosselló, R.; Tella Ferreiro, G. (Scientia gerundensis, 1992)
Most important aspects of a work titled 4ork oak Atlas of Extremaduran are presented here. A set of maps about: cork oak stands distribution; cork quality in the several zones; and ecological factors wich may limit the appearence of cork oak stands, are elaborated from the availahle thematic cartography. The Geographical Information SystemPC-ARC-IhFO ha beenused to get it. The final result is the Land Suitability for Cork Oak and Cork Quality Map of Extremadura. This map defines for the whole studied area the relative cork quaiity to be obteined and the presence of ecological factors wich may be adverse or exclusive for cork oak.
Keywords: Cork oak; Cork quality; land classification; Quercus suber; thematic cartography

Primeros ensayos de inducción de embriones somáticos de Quercus suber L. - Bueno, A. J.; Manzanera, M. A. (Scientia gerundensis, 1992)
Susceptibility of cork oak (Quercus suber L.) embryos, endosperm and ovules to somatic embryogenesis induction has been studied. 2,4-D at different concentrations was tested. Samples were collected every two weeks, dong the fruit development period, from June till September. The embryos formed callus, from which globular and heart and torpedo-shaped structures and somatic embryos at different developing degrees were obtained.
Keywords: Cork oak; Quercus suber; Somatic embryogenesis; tissue culture; vegetative propagation

Thermal decomposition of wood in oxidizing atmosphere. A kinetic study from non-isothermal TG experiments - Cordero, T; Rodriguez-Maroto, J M (Thermochimica acta, 1991)
The kinetics of thermal decomposition of four wood species in oxygen-bearing atmo- spheres of 5, 10 and 20% molar Oz concentrations have been studied from temperature-pro- grammed experiments carried out at 5, 10 and 20 K mm ’ -* heating rate. Devolatihzation as weII as combustion of the reaminin g solid have been considered to analyze the weight loss curves. The homogeneous volume reaction (VR) model has been used to describe devolatihza- tion, whereas for solid combustion the grain model has been also checked. A two-stage approach has been used to fit the conversion-time curves and to derive the corresponding apparent kinetic parameters. The VR/VR (pyrolysis/combustion) combination provided a better description of the experimental (~-1 curves than the VR/grain combination. Hohn oak and cork oak showed very close reactivities, whereas some differences were observed for aleppo pine and eucalyptus.
Keywords: Aleppo pine; combustion (voyant); Cork oak; EUCALYPTUS; Holm oak; Kinetic model; pyrolysis; Wood

Micropropagation of juvenile and adult Quercus suber L. - Manzanera, J A; Pardos, J A (Plant Cell, Tissue and Organ Culture, 1990)
This paper describes research on the application of tissue culture techniques to the micropropagation of cork oak (Quercus suber L.), a forest species of ecological and industrial importance in the Mediterranean area. Apical buds and nodal stem segments were employed as initial explants. Their origins were young seedlings, stump sprouts and sprouts formed on cuttings collected from old trees. The action of the mineral medium and growth regulators was studied in the multiplication stage. Media with low concentrations of ions, such as Sommer's or Heller's, are more suitable for growth and proliferation of explants than other media richer in salts. It was also observed that cytokinin (BA) must be present for the culture development. Adding low concentrations of auxin (NAA) to the medium improves the multi- plication rate, especially in vegetative material of adult origin. The auxin type is the most important factor in the promotion of rhizogenesis. The method of application determines the quality of the root system. Treatment with low concentrations of IBA added to the rooting medium gives the best results. High sucrose concentration also improves rooting. Diluting the mineral rooting medium is slightly favourable, although there is no significant difference between it and the standard mineral concentration.
Keywords: Cork oak; micropropagation; Quercus suber; rooting; tissue culture

Dieback of cork oak (Quercus suber) in Catalonia (NE Spain) caused by Botryosphaeria stevensii - LUQUE, J; Girbal, J (European Journal of Forest Pathology, 1989)
Botryosphaeria stevensii Shoemaker (anamorph: Diplodia mutila Fr. apud Mont.) is reported as the cause of canker and dieback of cork oak (Quercus suber L.) in Catalonia (NE Spain). It also causes wilting of trees after cork is removed for industrial purposes. Symptomatology and details of morphology for both anamorph and teleomorph are given.
Keywords: Botryosphaeria stevensii; canker; Cork oak; dieback; diplodia mutila; morphology (PG); Symptoms

Los alcornocales de la provincia de Girona. - Vilar, L; Polo, L; Planella, D (Scientia gerundensis, 1989)
A first attempt to typify the ecology of cork oak in Girona country (NE part of Iberian Peninsula) is done. The evolution of forest cork oak grove's areas in recent decades is given. We found that it is in regression and it would be necessary urgent actions to recuperate it.
Keywords: Cork oak; cork oak grove; ecological typification; forest evolution; Girona country

The Twig Wasp of Cork Oak - Its Biology and Control - BAILEY, STANLEY F.; STANGE, LIONEL A. (Journal of Economic Entomology, 1966)
Cork oak (Quercus suber L.), the principal source of commercial cork, was introduced to this country in 1858 from acorns sent from Spain. For Many years no pests were noted. In 191R the twig wasp Plagiotrochus suberi Weld, not described until 1926, was observed injuring the tree in California. It has since become a pest, particularly when the cork oak is planted as an ornamental or shade tree. The larvae feed within a jellylike matrix in the small twigs. The resulting dead twigs on the infested trees pn,- sent an unsightly, brushy appearance. The wasp has 1 generation a year. The agamic females emerge from the twigs via a small round hole in May. They are very weak fliers and remain close to the twigs on which they originated. Oviposition is in the twig growth of the previous year. The eggs hatch in late summer and the larvae develop slowly, pupating the following April. The insect has been found in Switzerland and Portugal (where it probably originated) only in the past few years. The time and manner of introduction into California are not known. In North America the wasp is found only in California. Only moderate control has been obtained with sprays of lindane and carbaryl directed against the adult stage. A European aphid, Myzocallis borneri Stroyan, is now a pest of the cork oak in California. This record is new. Other insect pests of the tree in this country are of very minor importance.
The following values have no corresponding Zotero field: label: California;Plagiotrochus suberi;cork oak;twig wasp (PG)
Keywords: California; Cork oak; Plagiotrochus suberi; twig wasp (PG)